A probabilistic pedotransfer function for estimating the soil water characteristic curve and quantifying its uncertainty - Xin-Yuan Wang; He-Fu Pu; Ming Min; Yu Miao; Sen-Lin Xie; Xiao He (Computers and Geotechnics, 2027)

Metabolic redirection and capacity expansion in heterotroph-reinforced microalgae-methanotroph systems under high ammonia stress - Yong-Ze Lu; Jia-Sen Yang; Xin-Ya Tan; Yi-Ru Wang; Hong-Yin Sha; Hao-Yu Wang; Shao-Jie Zong; Guang-Can Zhu (Bioresource Technology, 2027)

Hollow Li/Al-LDH architecture engineering to accelerate mass transfer for high-efficiency low-grade lithium extraction - Chenghao Qiu; Yujiao Cao; Haiping Su; Jun Chen; Jianguo Yu; Sen Lin (Desalination, 2026)

Cane water content regulates grapevine (Vitis vinifera L.) winter bud dormancy via ros homeostasis and antioxidant enzyme system - Wen-Qin Hua; Song-Yu Li; You-Mei Li; Zhao-Sen Xie (Molecular Biology Reports, 2026)

Molecular epidemiology and antimicrobial resistance of Vibrio parahaemolyticus isolates from aquatic products in the Southern Fujian coast, China - Qiao-Hua Zheng; Yang Chen; Yu-Fang Tian; Turmidzi Fath; Jun-Chao Zheng; Dan-Feng Zhang; Yi-Hong Wang; Qing-Sen Chen; Feng-Xia Li; Xiu-Min Chen; Yuan-Qing Hu (Brazilian Journal of Microbiology, 2026)

Endophytic fungi mediate litter decomposition dynamics through microbial interactions and temporal shifts - Yuan-Qi Zhao; Fu-Sen Nan; Xiao-Qian Yang; Jian-Fei Yu; Han-Yue Bi; Si-Jun Duan; Xin-Yue Wang; Tian-Ci Chen; Qin-Jiang Mao; Xiao-Bo Wang (Soil Biology and Biochemistry, 2026)

Biocontrol potential of Bacillus velezensis lut-Y1: Antifungal lipopeptides against postharvest fungi Alternaria alternata and Penicillium expansum - Hui-Jun Yuan; Yan-Sen Li; Wen-Jin Ma; Tian-Kun Zhao; Zhen-Dong Wang; Miao-Miao He; Shi-Man Yu; Yan-Ying Xu (Physiological and Molecular Plant Pathology, 2026)

Lunar transient atmosphere recorded in Chang'e 6 impact glass beads - Ziyan Han; Hejiu Hui; Sen Hu; Zhiyong Xiao; Fanglu Luo; Di Zhang; Yutao Lin; Huicun He; Liang Gao; Yue Zhang; Wenxin Ouyang; Yu Li; et al. (Earth and Planetary Science Letters, 2026)

Efficient lithium recovery and valorization from high‑sodium industrial wastewater - Yujiao Cao; Chenghao Qiu; Zhiheng Chen; Jun Chen; Jianguo Yu; Sen Lin (Chemical Engineering Journal, 2026)

Aerogel-based photothermal materials for environmental remediation and solar energy utilization: Materials chemistry, mechanisms, structural design, and applications - Tong Jing; Meng Dai; Fangying Hong; Huijun Yu; Sen Wang; Liang Guo; Tianguang Lu; Shuguang Wang; Zuoli He (Journal of Environmental Chemical Engineering, 2026)

High-efficiency electro-reductive nitrate-nitrogen denitrification on Cu-modified N-doped carbon with highly active Cu-N2 sites - Qingting Ma; Yujuan Chen; Sen Li; Xin Li; Xiaofang Yu (Journal of Environmental Chemical Engineering, 2026)

Rocking behavior of prestressed concrete-filled steel tubular lattice towers under compression-bending-torsion loading - Yu-Sen Liu; Xu-Hong Zhou; Ji-Chun Liu; Lei Pei; Wenyan Zeng; Yu-Hang Wang (Engineering Structures, 2026)

Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Manganese-based activated carbon composites promote nitrogen removal in low temperature constructed wetlands via enhanced extracellular electron transfer - Deliang Chen; Yuying Wang; Aoli Cao; Yu Hou; Fanlong Kong; Jiaxin Shi; Sen Wang (Environmental Research, 2026)

Postprocedural pain after microwave ablation versus cryoablation for pulmonary tumors: A retrospective comparative study - Hao-Yun Liu; Wen-Jeng Lee; Hsin-Ming Chen; Chiueng-Fang Wu; Pei-Ming Huang; Jang-Ming Lee; Yu-Sen Huang; Yeun-Chung Chang; Wei-Chun Ko (Cryobiology, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

Menaquinone-4 protects CD8+ T cells from ferroptosis to enhance anti-tumor immunity - Jiarong Wang; Wen Wang; Simiao Fan; Liyun Liang; Huaibin Hu; Zenqing Song; Yu Zhang; Jiamei Zhang; Wanying Xiao; Biyu Zhang; Yaxin Li; Liang Luo; et al. (Science China Life Sciences, 2026)

Microseismic localization method based on adaptive residual neural network with layered medium model - Sen Hua; Liyuan Yu; Zhuangcai Tian; Minghe Ju; Hongwen Jing (Journal of Applied Geophysics, 2026)

Sedimentation rate changes revealing the evolution of circum–Arctic ice sheets since the Last Interglacial - Song Zhao; Dong Wu; Yu-Ying Zhang; Chao Cui; Sen Shan; Peng Ren; Lin-Sen Dong; Wei-Bin Zhang; Shu-Wei Sun; Yan-Guang Liu (Global and Planetary Change, 2026)

Characterizing brain structural and functional abnormalities in borderline personality disorder by seed-based d mapping approach - Wanru Qiu; Sen Li; Aoxue Zhang; Hao Yu; Jian Cui; Yinghong Xu; Liangliang Ping; Hao Zheng; Chunyu Dong; Kun Li; Cong Zhou (Brain Imaging and Behavior, 2026)

Molecular unraveling of Li+-solvent interaction reversal and its impact on low-temperature desolvation for weakly solvated electrolytes - Yanyan Zhang; Yuxin Liu; Jia-Yan Liang; Min Niu; Yu Zhang; Xingyu Chen; Lulu Fu; Shuang-Yan Lang; Sen Xin; Chunhui Yang; Fuyi Wang; Yu-Guo Guo (Science Bulletin, 2026)

Mean warming enhances insect resilience to high temperatures: species-specific evidence from two wheat aphids - Xue-Jing Wang; Yu Wang; Shu-Lin Ning; Jia-Qi Li; Biao Cui; Long-Fei Yue; Li-Yan Wang; Chun-Sen Ma (Journal of Insect Physiology, 2026)

Application of short-wave infrared spectroscopy in sandstone-type uranium deposits: A case study of the Yuejin-II uranium deposit in the Qaidam Basin, China - Wen-Yi Wu; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Yi-Han Lin; Yan Zhou; Chen Zhang; Ruo-Yu Shi; Xue-Feng Gao; Duo Wang; Bin Guo; Xiao-Qin Xu; et al. (Journal of Geochemical Exploration, 2026)

Functional antagonism and underlying regulatory pathways of haptoglobin splicing isoforms in the immune response of half-smooth tongue sole (Cynoglossus semilaevis) - Suxu Tan; Yixiao Hu; Wenwen Wang; Sen Han; Yu Bai; Yishuai Li; Kunpeng Shi; Shaoqing Zang; Yiming Hu; Zhenxia Sha (Fish & Shellfish Immunology, 2026)

Synergistic adsorption and reduction of uranium(VI) by nZVI@COFs composite with enhanced performance - Mengqi Ma; Chuhan Qiu; Huaichang Yu; Xiao Shen; Baowei Hu; Sen Yang (Chemical Engineering Journal, 2026)

Microbial electrosynthesis of methane in an up-scaled zero-gap cell - Bin Bian; Xinrui Ma; Sen Li; Najiaowa Yu; Chenghan Xie; Wulin Yang; Bruce E. Logan (Water Research, 2026)

Static and dynamic responses of a novel UEST column under axial compression and wave force - Yun-Long Chen; Jing-Zhong Tong; Li-Sen Zheng; Chao-Qun Yu (Ocean Engineering, 2026)

Integrated transcriptomic and metabolomic analyses reveal the mechanism of hypoxia tolerance in Aspergillus chevalieri under controlled nitrogen atmosphere - Yu-Liang Qin; Jing Ren; Wen-Bo Sun; Ying-Ying Wang; Shuai-Bing Zhang; Yang-Yong Lv; Huan-Chen Zhai; Yuan-Sen Hu (International Journal of Food Microbiology, 2026)

Carbon amendment drives microbial community to favor dissimilatory nitrate reduction to ammonium over denitrification in paddy soil - Mingzi Shi; Sen Zhang; Kejia Yu; Yuqi Zhang; Yikai Zhou; Yicai Yao; Wang Zhou; Yuhe Wang; Hongge Chen; Mingdao Wang (European Journal of Soil Biology, 2026)

Tailoring texture for dysphagia diets: Unraveling the synergistic role of protein and blended vegetable oil in softening starch gels - Mengdi Cai; Hongwei Cao; Yu Zhang; Kai Huang; Sen Li; Hongdong Song; Xiao Guan (Carbohydrate Polymers, 2026)

Laver cultivation mitigates zooplankton miniaturization in eutrophic coastal ecosystems - Sen Li; Jieqing Yang; Jinchen Yu; Tao Sun; Shuo Chen; Jin Zhou; Peng Zhang; Hong Huang (Hydrobiologia, 2026)

Antimicrobial and Antitumor Activities of Endophytic Fungi from the Medicinal Plant Paris polyphylla var. yunnanensis - Jing Zhang; Hao-Lin Yu; Yu Zhang; Chen-Sen Xu; Chao Wang; Yi-Lin Liu; Yi-Bo Shen; Jin-Zhong Hu; Zhi-Xin Liao (Current Microbiology, 2026)

Evaluation of different types of isotope-labelled steroids based on liquid chromatography–mass spectrometry - Yameng Zhao; Luqi Sun; Pengshuai Zhang; Sen Xu; Shenghao Zhu; Lantao Zhang; Mingyang Hu; Jinglan Yu; Zhaocong Shang; Lin Zou; Wen Lei (Isotopes in Environmental and Health Studies, 2026)

Super retarding-flame wood - Sen Gao; Jing Ren; Baoping Zhang; Lixian Yang; Yiqiang Wu; Yingying Zhang; Leitao Cao; Qing Li; Chunlei Zhang; Mingyue Miao; Haipeng Yu; Shouxin Liu; et al. (Science Bulletin, 2026)

Tumor-associated bacterial effectors: novel frontiers in tumor biology and immunity - Jia-Hao Dai; Ying-Qi Lu; Sen-Yu Feng; Xi-Rong Tan; Li-Li Li; Yue-Can Zeng; Jian-Zhou Chen; Jun Ma; Na Liu (Science Bulletin, 2026)

A laminated 3D desalinator with 3D energy trapping effect for high-efficient solar steam generation and desalination - Sen Ai; Zhi-Han Zhou; Cheng-Yu He; Bao-Hua Liu; Gang Liu; Jun-Shuai Li; Xiang-Hu Gao (Process Safety and Environmental Protection, 2026)

Anti-leukemia steroidal saponins from Paris polyphylla var. yunnanensis - Yu Zhang; Yu-Chen Zhang; Yu-Chen Fan; Chen-Sen Xu; Hao-Lin Yu; Chao Wang; Jing Zhang; Yi-Lin Liu; Yi-Bo Shen; Chao Liu; Jin-Yue Sun; Jin-Zhong Hu; et al. (Phytochemistry, 2026)

Nanofiber engineering of covalent organic frameworks via monomer–solvent synergy for high-efficiency uranium capture - Xiao-yi Tang; Qun-yan Wu; Yi-chen Huang; Peng-fei An; Lin Wang; Ji-pan Yu; Shu-sen Chen; Zi-jie Li; Li-yong Yuan; Wang-suo Wu; Zhi-fang Chai; Wei-qun Shi (Journal of Hazardous Materials, 2026)

Dynamics and drivers of last-resort antibiotic resistance genes during pilot-scale aerobic fermentation of municipal sludge and subsequent bok choy pot trials - Li-Tao Zhou; Da-Hai He; Jiang Li; Ruo-Xue He; Shi-Jin Ma; Guang-Yu Gong; Xiao-Shuang Zou; Sen Li; You-Fei Zhou; Wei-Jie Hu (Journal of Hazardous Materials, 2026)

Mechanisms of oat dough adhesion modulated by moisture-controlled roasting: The role of aqueous extracts - Binghua Sun; Ruige Yu; Xiaojie Qian; Fan Yang; Sen Ma; Chong Liu; Xiaoxi Wang (Food Hydrocolloids, 2026)

Design Rules for Robust Coronary Artery Segmentation: A Systematic Analysis of Dataset Size, Windowing, Architectures, and Vessel Geometry - Ming-Hui Hung; Yu-Wei Chiang; Hao-Yun Liu; Han-Hsuan Chu; Yu-Sen Huang; Pin-Yi Chiang; Hsin-Ming Chen; Tzung-Dau Wang; Shyh-Jye Chen; Wen-Jeng Lee (Annals of Biomedical Engineering, 2026)

Integrated metabolomics and transcriptomics analysis of dynamic changes in non-volatile compounds during blueberry fruit ripening - Sen Cao; Yu Zhang; Jiaying Jin; Zhibing Zhao; Donglan Luo; Liangjie Ba (Postharvest Biology and Technology, 2026)

The interactive effects of roasting degree and lipid content on the gas retention capacity in fermented oat dough - Fan Yang; Wenhua Ma; Ruige Yu; Binghua Sun; Xiaojie Qian; Cong Sun; Chong Liu; Sen Ma; Xiaoxi Wang (Food Research International, 2026)

Sn2+ doping-induced activation of inert adsorption sites in Li/Al-LDHs for selective lithium extraction from brines - Rui Zhang; Chenlu Yan; Jun Chen; Ting Wei; Jianguo Yu; Sen Lin (Chemical Engineering Journal, 2026)

Promoting low-temperature lager beer production by redox potential-controlled fermentation - Zhen-Yu Huang; Hua Yin; Sen Liu; Jia-Jie Zhang; Cui Zhang; Lei Xing; Xiao-Yan Huang; Feng-Wu Bai; Chen-Guang Liu (Biocatalysis and Agricultural Biotechnology, 2026)

miR-486-3p Suppresses Osteosarcoma Proliferation and Migration by Targeting the SPRED1-MAPK/ERK Pathway - Yu Zhang; Yi Zhou; Sen Zhang; Xiaoying Zhang; Jiaxin Li; Xiao-Kai Zhan (Biochemical Genetics, 2026)

Overexpression of wheat Wcor80 confers tolerance to low temperature in transgenic plant - Luyao Wang; Jiaang Cao; Xuesong Wang; Junbao Zhang; Yushu Chen; Sen Yang; Qingyi Shao; Mengdi Yu; Zhongmin Jin; Lijie Liu (Transgenic Research, 2026)

Biotic interactions driving the Centropages species co-existence in temporal Xiangshan Bay, China - Jieqing Yang; Yunrong Shi; Jinchen Yu; Lang Chen; Yuekai Wang; Tao Sun; Sen Li; Xinran Li; Qinghe Liu; Jing Fu; Wei Tian; Jin Zhou (Journal of Oceanology and Limnology, 2026)

Quantifying the cooling performance of urban tree diversity using remote sensing: A case study of a semi-arid megacity (Xi'an, China) - Nuoting Hou; Sen Wang; Jianhong Liu; Lei Wang; Jun Wang; Xuhong Wang; Liu Yang; Nan Liu; Yu Zhu (Urban Climate, 2026)

Tetrahydrofuran- and dihydrofuran-containing nor-clerodane diterpenoids from Teucrium viscidum: Isolation, stereochemical assignment, and anti-hepatic fibrosis activity - Xin-Yi Hu; Lu Gan; Fei-Yu Zhang; Guang-Hai Zhu; Yi-Ling Liao; Guo-Sen Huang; De-an Guo; Wei Li (Phytochemistry, 2026)

Effect of saponin extracts of quinoa on postharvest preservation of asparagus and its mechanism - Jiehan Zhang; Sen Li; Qianqian Wang; Yao Lu; Wei Zheng; Yu Zhang; Xiao Guan (Journal of Stored Products Research, 2026)

Temporal dynamics of insecticide-resistance mutations in the diamondback moth Plutella xylostella (Linnaeus, 1758) within northern immigration regions - Ya-Jun Qu; Jin-Cui Chen; Hui-Juan Li; Shuai-Yu Wang; Xue-Yan Zhang; Ary A. Hoffmann; Sen-Shan Wang; Shu-Jun Wei (Journal of Asia-Pacific Entomology, 2026)

Micro-structure alteration of gas-bearing shale induced by CO2-O2-water-rock reactions: Experiments vs. numerical simulation - Qi Yu; Danqing Liu; Sen Yang; Yuan Feng; Zexing Zhang; Hong Kou; Yilian Li (Gas Science and Engineering, 2026)

Effects of thermal drying methods on characteristic volatile organic compounds in Rosa roxburghii pomace - Lingshuai Meng; Tingting Zheng; Qingsong Zhou; Faping Mao; Yu Nie; Xu Song; Sen Cao; Su Xu (Food Chemistry, 2026)

Synergistic mechanism of hydrophobic and hydrophilic antioxidants in the interface of tree peony seed oil bilayer emulsion - Wen-Sen He; Na Wei; Jingyu Li; Qingzhi Wang; Haonan Yang; Chen Tan; Shouhe Huang; Huafang Ding; Jianhua Zhu; Hanyu Zhu; Zhen-Yu Chen (Food Chemistry, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Enhanced uranium (VI) removal in aqueous solutions via synergistic adsorption-reduction by phytic acid-modified MXene supported nZVI - Huaichang Yu; Mengqi Ma; Sisi Chu; Juanjuan Jiang; Linshan Fang; Tingting Sheng; Xiaoyu Li; Chuhan Qiu; Baowei Hu; Sen Yang (Chemical Engineering Journal, 2026)

Ribavirin acts as a candidate insect growth regulator: Providing sustainable control potential for Rhopalosiphum padi - Li Xu; Jingkun Li; Fei Miao; Zhiwen Zhao; Yichen Fu; Hengxu Yan; Sen Huang; Hao Yu; Runqiang Liu; Dongzhi Li (Crop Protection, 2026)

An efficient strategy to separate nanoplastics from water using anisotropic magnetic Janus particles - Ruiqi Yan; Sen Lin; Xia Yu; Lei Zhang; Jiaxi Wang; Wentao Zhao; Mingyang Xing; Qian Sui (Water Research, 2026)

The function of the alternative oxidase gene in the tolerance of Fusarium graminearum to azoxystrobin - Hao-Jie Sun; Yu-Liang Qin; Yi-Wen Feng; Ying-Ying Wang; Huan-Chen Zhai; Yang-Yong Lv; Yuan-Sen Hu; Shuai-Bing Zhang; Liang Huang (Pesticide Biochemistry and Physiology, 2026)

Seasonal dynamics of plankton networks and copepod selection strategies in the laver cultivation area of Haizhou Bay, China: based on sparse correlations for compositional data analysis - Sen Li; Hong Huang; Jinchen Yu; Tao Sun; Shuo Chen; Jin Zhou; Yunrong Shi; Peng Zhang; Jieqing Yang (Marine Environmental Research, 2026)

Oil-phase modulated molecular assembly in rice bran protein fibril-chitin nanofiber emulsion gels: Structural design strategy for synchronized fat replacement and sodium release optimization - Yao Feng; Yu Zhang; Kai Huang; Sen Li; Hongwei Cao; Zhenliang Sun; Xiao Guan (Food Research International, 2026)

Dual-phase anion engineering for boosting lithium capture by Li/Al-LDHs - Yujiao Cao; Chenghao Qiu; Jipeng Li; Jun Chen; Jianguo Yu; Sen Lin (Desalination, 2026)

Roles of vertical light-conducting carriers applied in microalgal-bacterial biofilm for enhanced nitrogen and phosphorus removal - Yong-Sen Cao; Yong-Qi Cheng; Yi Liu; Xing-Rui Zhou; Cong-Cong Tang; Zhang-Wei He; Wen-Qiong Wang; Yu Tian; Xiaochang C. Wang (Bioresource Technology, 2026)

Community assembly governs microbial biogeography and ecosystem multifunctionality across Tibetan alpine grasslands - Xiao-Qian Yang; Jian-Guo Ma; Jian-Fei Yu; Fu-Sen Nan; Yuan-Qi Zhao; Xiao-Bo Wang (Applied Soil Ecology, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Evaluating the role of ride-hailing in multimodal travel to maximize travel utility in urban areas - Yu Bai; Yuanqing Wang; Sen Wei; Yajuan Deng (Travel Behaviour and Society, 2026)

Microplastics and nanoplastics, emerging pollutants, increased the risk of pulmonary fibrosis in vivo and in vitro: A comparative evaluation of their potential toxicity effects with different polymers and size - Jia-Yi Dou; Sen Liu; Chen-Yu Wang; Xu Dai; Li-Hua Lian; Zhen-Yu Cui; Ji-Xing Nan; Yan-Ling Wu (Toxicology, 2026)

Integrated transcriptomic and physiological analysis highlights the candidate genes regulating enzymatic browning, antioxidant capacity, and lipid metabolism in pomegranate aril browning - Yawen Shen; Sen Wang; Ran Wan; Jian Jiao; Yujie Zhao; Liu Cong; Kunxi Zhang; Pengbo Hao; Yu Liu; Wanyu Xu; Miaomiao Wang; Jiangli Shi; et al. (Postharvest Biology and Technology, 2026)

Advances in the production of emulsifying pea protein isolates with the oat β-glucan glycosylation - Kai Huang; Hanwen Liang; Yu Zhang; Sen Li; Hongwei Cao; Hongdong Song; Wenqian Zhao; Xiao Guan (Food Chemistry, 2026)

Cylindrical PVC pipe: 2D macro light trapper and macroscopic photoprotective tube for fabricating high-concentration brine desalinators? - Sen Ai; Cheng-Yu He; Bao-Hua Liu; Gang Liu; Jun-Shuai Li; Xiang-Hu Gao (Desalination, 2026)

Numerical investigation and ML-based formulation for conventional and modified suction caissons subjected to unidirectional and combined loadings - Kewen Zhu; Hang Feng; Jian Yu; Sen Li (Computers and Geotechnics, 2026)

Optimizing rural aquatic remediation: A novel TBEC-IMO composite approach for targeted removal of blackening and odor agents - Siao Zhang; Zeng Liu; Sen Wang; Siyu Yi; Lei Yu; Hao Wang (Bioresource Technology, 2026)

Optimizing microbial fuel cells for wastewater treatment: material advances, design strategies, and application frontiers - Sen Wang; Zhiwei Fan; Yanling Guan; Siyu Yi; Lei Yu; Fuping Li; Hao Wang (Environmental Science and Pollution Research, 2025)

Corylifol A ameliorates pancreatic cancer-associated cachexia by targeting TAOK3 in pancreatic cancer cells and targeting TAOK1 in skeletal muscle cells - Ke Yu; Rui-Qin Zhang; Nan Li; Qiong-Sen Wang; Jia Gu; Sai-Yue He; Ying-Qian Wang; Guo-Guo Wang; Xiong-Wen Zhang; Xiao-Dong Guo; Xuan Liu (Toxicology and Applied Pharmacology, 2025)

First report of Thraustochytrium caudivorum isolated from the undulated surf clam (Paratapes undulatus): Morphological, molecular, and ecological insights under climate change - Yu Chen; Seung-Hyeon Kim; Jinxia Long; S.D.N.K. Bathige; Hyoun Joong Kim; Sen-Lin Tang; Kyung-Il Park (Protist, 2025)

Strong carbonate buffering in karst cascade river-reservoir systems constrains CO2 production and emissions - Xuan Hu; Wanfa Wang; Lishan Ran; Sen Xu; Qiong Han; Francesco Ulloa-Cedamanos; Jun Zhong; Bei-Bei Chen; Shengde Yu; Dengming He; Wenhong Shi; Siqin Xu; et al. (Geochimica et Cosmochimica Acta, 2025)

Integration of E-nose, volatilomic profiling, and transcriptomics reveals the mechanisms aroma formation during the ripening process of blueberries - Jiaying Jin; Xiaogang Wang; Yu Zhang; Liangjie Ba; Su Xu; Lingshuai Meng; Xiaohong Kou; Sen Cao (Food Research International, 2025)

Construction of rice bran protein fibril/chitin nanofiber emulsion and emulsion gel system regulated by sodium chloride concentrations: a new perspective of fat-salt dual-function substitution - Yao Feng; Yu Zhang; Jing Liu; Kai Huang; Sen Li; Hongwei Cao; Xiao Guan (Food Chemistry, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Cellular indexing of transcriptomes and epitopes by sequencing unveils coordinated RNA and protein landscape in ovary at single-cell resolution - Yujuan Qi; Yuxuan Feng; Xiaoyan Liu; Jiaxin Li; Qiuru Huang; Zhenbei Li; Sen Zheng; Ning Chen; Jie Cheng; Xinhui Yang; Wei Tao; Xiangnan Cao; et al. (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Identification and Expression Analysis of Low-Temperature Stress Responsive MIKC-Type MADS-Box Gene Family in Wheat - Zhang Junbao; Chen Yushu; Wang Xuesong; Cao Jiaang; Yang Sen; Shao Qingyi; Yu Mengdi; Jin Zhongmin; Liu Lijie (Tropical Plant Biology, 2025)

Large-scale single tree information extraction of oil palm in Malaysia based on sub-meter visible light satellite images - Sen Zhang; Nan Li; Yaoping Cui; Jinwei Dong; Le Yu; Lishan Ran; Ziyue Chen; Jiqiang Niu; Wei Yan; Kasturi Devi Kanniah; Xiangming Xiao (Computers and Electronics in Agriculture, 2025)

Rational design of an ultra-high-gain MoS2 phototransistor enabling room-temperature detection of few-photon signals and attomolar-level immunosensing - Zhengdao Xie; Yun Hui; Wenhua Zhou; Shengxuan Xia; Yawei Lv; Liwei Ouyang; Yang Chai; Xingqiang Liu; Bei Jiang; Chang Liu; Sen Zhang; Chenchen Chu; et al. (Science Bulletin, 2025)

Physiological and transcriptomic analysis of salicylic acid on membrane lipid metabolism and cell wall metabolism in postharvest peach fruit - Guohe Zhang; Yu Zhang; Taomei Yang; Donglan Luo; Zhibing Zhao; Liangjie Ba; Su Xu; Jiangkuo Li; Sen Cao (Postharvest Biology and Technology, 2025)

Horizontally transferred NADAR genes contribute to immune defense of ladybird beetles against bacterial infection - Kun-Yu Yang; Yi-Fei Sun; Yuan-Sen Liang; Hao Li; Meng-Xue Qi; Zhaowei Wang; Luis Carlos Ramos Aguila; Li-Qun Cai; Hao-Sen Li; Hong Pang (Insect Biochemistry and Molecular Biology, 2025)

Effect of honey-aloe paste on alleviating loperamide-induced constipation, in relation to regulation on gastrointestinal function and intestinal microenvironment - Danni Chang; Fanhua Wu; Yu Yang; Jinjin Zhang; Tianchen Ma; Sen Guo; Haoan Zhao; Wei Cao (Food Research International, 2025)

Layer-by-layer assembly mechanism of particulate-continuous phase for sandwich-like nanoparticles in oral colon-targeted protein delivery - Wen-Xuan Hu; Chang-Sen Jin; Si-Lin Li; Jia-Yang Fu; Liang-Sen Liao; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

Mechanism of high intensity ultrasonic treatment combined with β-glucan affecting the structure of highland barley protein to improve the stability of highland barley milk - Hongwei Cao; Xiaotong Zhuang; Haojie Liu; Man Wang; Kai Huang; Hongdong Song; Sen Li; Yu Zhang; Zhenliang Sun; Xiao Guan (Food Hydrocolloids, 2025)

Low-tortuosity COFs-functionalized carbonized wood electrodes for efficient electrochemical extraction of uranium(VI) - Sen Yang; Huaichang Yu; Mengqi Ma; Xiaoyu Li; Tingting Sheng; Jiaxin Weng; Lei Zhou; Baowei Hu (Desalination, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Granulating-avoiding aluminum-based adsorbents for fast salt lake lithium extraction with low freshwater consumption - Yujiao Cao; Jun Chen; Sen Lin; Jianguo Yu (Chemical Engineering Journal, 2025)

Peripheral blood RNA modifications as a novel diagnostic signature for polycystic ovary syndrome - Liwen Zhang; Xinxin Liu; Yu Zhang; Lang Qin; Shijia Pan; Xueqi Yan; Sen Dong; Zerong Feng; Song-jia Fan; Rusong Zhao; Xueying Gao; Shigang Zhao; et al. (Science China Life Sciences, 2025)

Biotic and Abiotic Factors Shaping the Metacommunity Structure of Free‐Living Bacterioplankton and Nanoflagellates in the Kuroshio Region - Feng‐Hsun Chang; Ariana Chih‐Hsien Liu; Jinny Wu Yang; Hiroaki Saito; Yu Umezawa; Chung‐Chi Chen; Jan Sen; Chih‐hao Hsieh (Molecular Ecology, 2025)
Substantial community variation in free‐living bacterioplankton and their main predators—heterotrophic and mixotrophic nanoflagellates (HNFs)—often remains unexplained due to the frequent oversight of their mutual dependency through reciprocal influences. Here, we sampled bacterioplankton and HNFs from both the surface layer and the deep chlorophyll maximum (DCM) across a 13‐degree latitudinal transect in the Kuroshio, spanning from Taiwan to Japan. Using three‐way variation partitioning complemented by a null model approach, we disentangled the reciprocal influences between these microbial groups alongside the effects of dispersal and the abiotic environment. Our analyses reveal that bacterioplankton and nanoflagellates reciprocally explain over 10% of compositional variation when both layers are analysed together, highlighting the significance of their reciprocal influences. Dispersal contributes a comparable 10% of the explained variation, whereas environmental dissimilarity plays a minor role in shaping both trophic levels. When examining each layer separately, bacterioplankton composition is primarily driven by dispersal, whereas the composition of heterotrophic and mixotrophic nanoflagellates cannot be uniquely attributed to bacterioplankton, dispersal, or environmental factors. These findings suggest that biotic factors become more pronounced when considering vertical variation, whereas horizontal dispersal predominantly drives community composition within a given water layer. By incorporating two trophic levels, this study provides new insights into the metacommunity dynamics of free‐living bacterioplankton and HNFs, emphasising the role of their mutual influences across depth gradients.

Ribociclib derivative Rib-CA suppresses breast cancer progression via p53-dependent apoptosis - Mengwei Song; Ying Zhou; Xudong Yu; Boyu Zhang; Sen Wang; Kadirya Asan; Zihao Yang; Haiyan Lin; Jian Wang; Xiaoxue Song; Yongyuan Jiang; Si Chen; et al. (Toxicology and Applied Pharmacology, 2025)

Geochronology and geochemical characteristics of sulphides from Tianzuo hydrothermal field (63°32ʹ E), South West Indian Ridge - Parijat Roy; Koushick Sen; Surya Prakash L.; V. Yu Kuznetsov; Fedor Maksimov; Deepak Kumar; S.S. Sawant; Deepak Kumar Agarwal; Srinivas Rao A.; P. John Kurian (Marine and Petroleum Geology, 2025)

Synergistic dewatering of construction foundation sludge via tripartite strategy: High-efficiency flocculation and floc skeleton reinforcement mechanism - Shixin Zhang; Jiahui Zhang; Dilin He; Yixin Zhang; Shiyu Yuan; Xiaomin Tang; Huaili Zheng; Sen Li; Yuxin Chen; Yu Qin (Journal of Environmental Chemical Engineering, 2025)

Exploring the limit of Cu-based small-pore zeolite framework collapse during hydrothermal aging in NO abatement from diesel vehicle exhaust - Wenqing Ding; Yu Sun; Jinpeng Du; Zhongqi Liu; Jingjing Liu; Tongliang Zhang; Wenpo Shan; Xiaoyan Shi; Sen Xue; Xuewang Han; Yunbo Yu; Yulong Shan; et al. (Journal of Environmental Sciences, 2025)

Molecular docking screening of endogenous protease inhibitors in sea bass (Lates calcarifer) and in vitro validation of their inhibitory efficacy - Run-Jian Gao; Lu Sun; Sen-Di Zhou; Yu-Meng Liu; Wei-Qiang Qiu; Sheng-Ping Yang; Yun-Fang Qian (Food Bioscience, 2025)

Enhancing the formation rate and level of oat globulin fibrils by microwave heating: Elucidation of potential mechanisms - Mengdi Cai; Hongwei Cao; Sen Li; Hongdong Song; Yu Zhang; Kai Huang; Man Wang; Zhenliang Sun; Xiao Guan (Food Hydrocolloids, 2025)

Vertically aligned MXene@PB electrode by directional freeze-casting for simultaneous capacitive deionization of U(VI) and Cs(I) with enhanced performance - Sen Yang; Xiaoya Cheng; Huaichang Yu; Ji Lei; Weisheng Dai; Zitong Luan; Chia Chay Tay; Baowei Hu (Desalination, 2025)

Preparation of CeO2/biochar composites by flash Joule heating and the research on its efficient removal performance of VOCs - Lanxi Yu; Keliang Pan; Yi Tang; Wenyan Xu; Jin Chen; Renxi Fang; Yunzi Li; Chunjie Yan; Sen Zhou (Chemical Engineering Journal, 2025)

Role of permeability evolution induced by CO2 injection on CO2 storage and CH4 production in a low permeability reservoir - Danqing Liu; Zexing Zhang; Sen Yang; Qi Yu; Ramesh K. Agarwal; Yilian Li (Chemical Geology, 2025)

Senegenin ameliorates diabetic encephalopathy via promoting mitophagy and repressing NLRP3 inflammasome activation - Xiao-dan Yan; Yu Yang; Wan-ting Zhang; Qing-quan Kong; Xi-tong Zheng; Lin-sen Li; Qing Yu (Psychopharmacology, 2025)

The mobility of U(VI) associated with Fe(II)-induced transformation of schwertmannite and its reductive dissolution and re-precipitation in AMD environment - Chang He; Yu Ning; Yilian Li; Hongyan Guo; Zhe Yang; Sen Yang; Fengcheng Jiang (Applied Geochemistry, 2025)

Unveiling Unusual Ecofunctional Traits of Endozoicomonas Species Through Comprehensive Comparative Genomics - Sim Lin Lim; Ching‐Hsiang Chin; Yu‐Jing Chiou; Ming‐Tsung Hsu; Pei‐Wen Chiang; Hsing‐Ju Chen; Yung‐Chi Tu; Wen‐Shyong Tzou; Sen‐Lin Tang (Environmental Microbiology, 2025)
Endozoicomonas is an omnipresent marine bacterial genus, associated with various marine organisms, that contributes to host health, nutrient cycling and disease resistance. Nonetheless, its genomic features remain poorly characterised due to a paucity of high‐quality genomes. In this study, we sequenced 5 novel Endozoicomonas strains and re‐sequenced 1 known strain to improve genomic resolution. By integrating these 6 high‐quality genomes with 31 qualified published genomes, our pan‐genomic analysis revealed variation in genetic traits among clades. Notably, Endozoicomonas lacks quorum‐sensing capabilities, suggesting resistance to quorum quenching mechanisms. It also lacks the capacity to synthesise and transport vitamin B12, indicating that it does not supply this nutrient to holobionts. Remarkably, Endozoicomonas genomes encode 92 identified giant proteins (15–65 kbp). These proteins cluster into three major groups associated with antimicrobial peptide synthesis, exotoxin production and cell adhesion. Additionally, we found that Endozoicomonas has acquired prophages from diverse sources via infection or other types of gene transfer. Notably, CRISPR‐Cas sequences suggest evolutionary trajectories independent of both prophage acquisition and phylogenetic lineage, implying potential geographic influences or environmental pressures. This study provides new insights into the genomic diversity of Endozoicomonas and its genetic adaptations to diverse hosts.

Removal of emerging organic contaminants in a subsurface wastewater infiltration system: A preliminary study of microbial mechanism - Feng-Jiao Peng; Xing-Jun Feng; Sen Li; Xiao-Long Yu; Jun Chen; Shuang-Shuang Liu; Guang-Guo Ying; You-Sheng Liu (Water Research, 2025)

2,4-Epibrassinolide (EBR) inhibits blueberry softening by modulating energy charge levels, cell wall and phenylpropanoid metabolism - Sen Cao; Linxiang Qiao; Tianyu Huang; Caie Wu; Yu Zhang; Xiaohong Kou (Postharvest Biology and Technology, 2025)

Small eukaryotic plankton community and alpha diversity variability in the Kuroshio region - Ariana Chih-Hsien Liu; Feng-Hsun Chang; Jinny Wu Yang; Hiroaki Saito; Yu Umezawa; Chung-Chi Chen; Sen Jan; Chih-hao Hsieh (Marine Environmental Research, 2025)

Sulfide-driven denitrification process for low C/N ratio wastewater treatment - Chao Wang; Cong Yu; Sen Qiao (Journal of Environmental Management, 2025)

Influence of the strain rate on the deformation and failure of rocks with multiscale cracks - Yan-jie Feng; Cheng-zhi Qi; Fa Zhao; Tao Li; An-sen Gao; Xiao-yu Ma (Geomechanics for Energy and the Environment, 2025)

Influencing the retrogradation properties of potato mash through multi-scale structural modifications mediated by enzymatic hydrolysis forms - Hongwei Cao; Mengting Huang; Zhenhao Liu; Kai Huang; Man Wang; Hongdong Song; Sen Li; Yu Zhang; Zhenliang Sun; Xiao Guan (Food Chemistry, 2025)

Quinone-based electrode in electrochemical conversion of salinity gradient energy - Xia-Yue Yuan; Wei-Bin Zhang; Ashkar Batol; Xin-Yu Liu; Nan-Sen Zhou; Juan Zhou; Jie Feng; Jun-Hu Liu; Xue-Jing Ma (Chemical Engineering Journal, 2025)

Novel degradable piezoelectric-induced PHBV/CS/HA scaffolds to achieve dual effects of endogenous osteogenesis and antibacterial properties by piezoelectric stimulation and ultrasonic action - Cong Yang; Meilin Zhao; Ning Yu; Sen Wang; Yuanqiang Li; Hang Chen; Yan Xiong; Xiaonan Zhang; Ping Ji (Chemical Engineering Journal, 2025)

A UAV Oblique Photogrammetry-based Carbon Offset Potential Assessment Method for High-Density Communities: A Case Study in Shanghai, China - Xiangyu Yu; Jie Bai; Shunming Gong; Riyan Li; Xin Zhou; Sen Wei; Ming Cheng; Ke Xu (Building and Environment, 2025)

Adjustment of Effective Water Quality Evaluation Index for Subtropical Urban Rivers - Mengyue Zhang; Mingqiao Yu; Sen Ding; Zhao Li (Environmental Management, 2025)

Multidimensional exploration of the interactions and mechanisms between fat and salt: Saltiness perception, and taste perception and oxidation of fat - Yao Feng; Yu Zhang; Kai Huang; Sen Li; Hongwei Cao; Xiao Guan (Trends in Food Science & Technology, 2025)

Indoor plant removal of atmospheric CO₂ — Effects on indoor air quality improvement and carbon sequestration - Yu-Sen Chang; Ming-Yu Ho; Chun-Wei Wu; Yu-Jie Chang (Process Safety and Environmental Protection, 2025)

Geochemistry of sulfides from massive carbonate replacement type tin ore at Gaofeng, Dachang orefield: Insights into precipitation conditions and enrichment of critical metals - Yu-Pei Liu; Pei Ni; Jun-Yi Pan; Wen-Chao Su; Stefano Albanese; Jian-Ming Cui; Yuan-Feng Cai; Ming-Sen Fan; Zhi-Lin Cheng (Journal of Geochemical Exploration, 2025)

High-efficient and reversible capture of protein by oxidized and carboxymethylated starch nanocrystals: Understanding interaction mechanism and regulating complexation - Wen-Xuan Hu; Jia-Yang Fu; Liang-Sen Liao; Ping Wang; Kexin Wang; Chang-Sen Jin; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

A new perspective on understanding soil microplastics: Composition, influencing factors of the soil plastisphere, and its impacts on the environmental behavior of co-existing contaminants - Shuai Zhang; Jiajun Yu; Ji Wang; Hua Yang; Yuhong Fu; Mao Fu; Sen Li; Huifang Zhao; Yixiao Wu (Chemical Engineering Journal, 2025)

Comparative Analysis of Stent-Assisted Versus Non-Stent-Assisted Coiling in the Management of Ruptured Intracranial Aneurysms: A Systematic Review and Meta-Analysis - Yu-Hu Ma; Yong-Lin He; Xiao-Yue Zhang; Rui Shang; Hai-Tao Hu; Ting Wang; Sen Lin; Ya-Wen Pan; Chang-Wei Zhang (Translational Stroke Research, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Leonurine protects against cisplatin-induced ototoxicity through its anti-oxidation and anti-apoptosis properties - Zhen Zeng; Lei Han; Dingding Dong; Honghai Tang; Ziwen Gao; Shaowei Hu; Biyun Zhu; Sen Zhang; Yilai Shu; Yafeng Yu (Toxicology Letters, 2025)

Antitumor activity and mechanistic study of steroidal saponins from the rhizomes of Paris polyphylla var. yunnanensis - Yu Zhang; Yu-Chen Fan; Yu-Chen Zhang; Qing Li; Yun-Yun Su; Chen-Sen Xu; Hao-Lin Yu; Chao Wang; Jing Zhang; Zhi-Xin Liao (Phytochemistry, 2025)

Selective nitrogen removal in constructed wetlands enhanced by MnX-GAC (X=Fe or Zn): Performance, mechanism and removal pathway - Deliang Chen; Xianwen Fang; Lu Zhao; Aoli Cao; Yu Hou; Guoxian Yang; Sen Wang; Maomao Li; Fanlong Kong (Journal of Environmental Management, 2025)

Rice bran protein fibril and chitin nanofiber complexes as a new material for fat substitution and saltiness enhancement - Yao Feng; Yu Zhang; Kai Huang; Sen Li; Hongwei Cao; Pengxiao Zhang; Man Wang; Zhenliang Sun; Xiao Guan (Food Chemistry, 2025)

Physicochemical stability and digestive properties of emulsions fabricated using transglutaminase and heat-induced Grifola frondosa protein microgels - Shuxiao Li; Wei Wu; Sen Wang; Yu Wang; Lihong Chen; Juan Wu; Yu Cheng (Food Bioscience, 2025)

Ultra-stable CO2-aqueous foams for carbon sequestration and internal mineralization in cellular cements - Dingqiang Fan; Xue-Sen Lv; Jian-Xin Lu; Rui Yu; Wei She; Juhyuk Moon; Takafumi Noguchi; Chi Sun Poon (Chemical Engineering Journal, 2025)

Cycleift: A deep transfer learning model based on informer with cycle fine-tuning for water quality prediction - Yang Yu; Shixin Zhao; Lintong Han; Lin Peng; Yanmei Xu; Qiujin Tian; Sen Chen; Zuogang Yang; Qiude Li; Zuquan Hu (Stochastic Environmental Research and Risk Assessment, 2025)

Disruptions of white matter in adolescents with internet game disorder: evidence from seed-based d mapping - Hao Zheng; Chunyu Dong; Yu Wan; Hailong Shen; Sen Li; Shanling Ji; Jian Cui; Kun Li; Hao Yu; Chuanxin Liu; Cong Zhou (Brain Imaging and Behavior, 2025)

Effectively mitigated eutrophication risk by strong biological carbon pump (BCP) effect in karst reservoirs - Wenke Zhang; Wanfa Wang; Sen Xu; Qingqing Sun; Wenhong Shi; Jiayi Man; Shengde Yu; Yujing Yang; Wenxin Wu; Xia Hu; Qixin Wu; Pan Wu; et al. (Water Research, 2025)

A novel flocculant based on "happy molecules" for the efficient removal of NSAIDs and NOM complexes: Role of parallel π-π stacking force - Shixin Zhang; Wenli Li; Yu Qin; Yao Chen; Zhen Liu; Sen Li; Longqing Tang; Huaili Zheng; Xiaomin Tang (Journal of Hazardous Materials, 2025)

Effect of persulfate stimulation on matrix alteration and permeability enhancement of fractured shale: Core-flooding experiments and numerical simulation - Sen Yang; Jinhao Yu; Danqing Liu; Yilian Li (Gas Science and Engineering, 2025)

Untargeted metabolomics and network pharmacology reveal the uric acid-lowering effects of alcohol extract of Gnaphalium affine and its extracts in hyperuricemic rats - Chen Wang; Xinchao He; Lijuan Rao; Jiajing Liao; Jin Qian; Xuefeng Yu; Sen Mei; Suqin Lin; Linqian Xu; Guiming Fu; Yin Wan (Food Bioscience, 2025)

Comparing Cr(III) oxidation intermediated by different manganese oxidizing bacteria: Efficiencies, kinetic and key structure characteristics of biogenic manganese oxides - Guangyuan Tu; Chunyu Ou; Qi Liao; Xiaoming Zhang; Shuangle Hou; Lin Yu; Kun Li; Sen Yang; Qi Li; Weichun Yang; Qingzhu Li; Mengying Si; et al. (Environmental Research, 2025)

Spatial patterns of essential fish habitats in the western Taiwan coast - Yu-Jia Lin; Chien-Cheng Lai; Hsu-Sen Chen; Tsu-Chun Chen; Kuo-Shu Chen; Norhafiz Hanafi; Pei-Jie Meng; Ying-Chin Fang; Chiee-Young Chen; Hsin-Ming Yen; Meng-Hsien Chen (Estuarine, Coastal and Shelf Science, 2025)

Fe-Mn bimetallic sulfide enhanced persulfate activation for monochlorobenzene degradation in groundwater: Performance, mechanism and applicability - Zhi Feng; Jinhao Yu; Zhe Yang; Danqing Liu; Jiali Xu; Yu Ning; Fengcheng Jiang; Sen Yang; Yilian Li (Chemical Engineering Journal, 2025)

Unveiling the Hidden Impact: Hematoma Volumes Unravel Circuit Disruptions in Intracerebral Hemorrhage - Yingqing Wu; Qin Deng; Ranran Wei; Sen Chen; Fusheng Ding; Haipeng Yu; Ning Hu; Shilei Hao; Bochu Wang (Translational Stroke Research, 2025)

Synaptic-mitochondrial transport: mechanisms in neural adaptation and degeneration - Yang Ding; Huan Yang; Jie Gao; Can Tang; Yu-Yuan Peng; Xin-Mei Ma; Sen Li; Hai-Yan Wang; Xiu-Min Lu; Yong-Tang Wang (Molecular and Cellular Biochemistry, 2025)

3D printed microtissue cassettes enabling high throughput proton radiobiological assays - Chih-Tsung Yang; I-Chun Cho; Ching-Fang Yu; Edward Cheah; Tesi Liu; Yi-Ping Lin; Sing-Yu Hu; Jyun-Wei Jheng; Ivan Kempson; Tsi-Chian Chao; Sen-Hao Lee; Eva Bezak; et al. (Analytica Chimica Acta, 2025)

A lightweight YOLO network using temporal features for high-resolution sonar segmentation - Sen Gao; Wei Guo; Gaofei Xu; Ben Liu; Yu Sun; Bo Yuan (Frontiers in Marine Science, 2025)
Introduction High-resolution sonar systems are critical for underwater robots to obtain precise environmental perception. However, the computational demands of processing sonar imagery in real-time pose significant challenges for autonomous underwater vehicles (AUVs) operating in dynamic environments. Current segmentation methods often struggle to balance processing speed with accuracy. Methods We propose a novel YOLO-based segmentation framework featuring: (1) A lightweight backbone(ghostnet) network optimized for sonar imagery processing (2) A bypass BiLSTM network for temporal feature learning across consecutive frames. The system processes non-keyframes by predicting semantic vectors through the trained BiLSTM model, selectively skipping computational layers to enhance efficiency. The model was trained and evaluated on a high-resolution sonar dataset collected using an AUV-mounted Oculus MD750d multibeam forward-looking sonar in two distinct underwater environments. Results Implementation on Nvidia Jetson TX2 demonstrated significant performance improvements. (1) Processing latency reduced to 87.4 ms (keyframes) and 35.3 ms (non-keyframes)(2)Maintained competitive segmentation accuracy compared to conventional methods and achieved low latency. Discussion The proposed architecture successfully addresses the speed-accuracy trade-off in sonar image segmentation through its innovative temporal feature utilization and computational skipping mechanism. The significant latency reduction enables more responsive AUV navigation without compromising perception quality. The newly introduced dataset fills an important gap in high-resolution sonar benchmarking. Future work will focus on optimizing the keyframe selection algorithm and expanding the dataset to include more complex underwater scenarios.

Highly efficient removal of per- and polyfluoroalkyl substances by extrusion-regenerated aminated polyurethane sponges - Xinhao Wang; Hanyang Chen; Wenran Wang; Xiufang Shen; Jiabao Wang; Sen Chen; Xueru Yu; Chew Tin Lee; Zhanghao Chen; Cheng Gu (Water Research, 2025)

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

Numerical investigation of sloshing flow interaction with porous baffles in a 2D rectangular tank - Yu-Jin Dong; Sen Wang; Guo-Hai Dong (Ocean Engineering, 2025)

Salt pollution acts as a photothermal material in an SSAC-based inverted bilayered desalinating evaporator assembled with a light trapper - Sen Ai; Yi-Nuo Wang; Cheng-Yu He; Bao-Hua Liu; Gang Liu; Jun-Shuai Li; Xiang-Hu Gao (Journal of Water Process Engineering, 2025)

Comparative analysis of different drying methods in the production of solid oat milk beverages: Insights into physicochemical properties and quality attributes - Kai Huang; Shanmei Zeng; Min Zhang; Hanwen Liang; Yu Zhang; Sen Li; Hongwei Cao; Wenqian Zhao; Xiao Guan (Journal of Cereal Science, 2025)

Effective SSR markers for assessing population structure, genetic diversity, and volatile compounds in Atractylodis Rhizoma - Haotian Zhong; Lina Chen; Lei Chen; Xiao Huang; Ling Gong; Juan Hu; Yuling Zeng; Kun Yu; Lin Sen (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Polymetallic Te-rich melts contribute to efficient enrichment and precipitation of Au in hydrothermal ore deposits - Gao-Hua Fan; Jian-Wei Li; Ri-Chen Zhong; Sarah A. Gleeson; Zhuo-Sen Yao; Daniel E. Harlov; Xiao-Dong Deng; Hao Cui; Chang Yu; Wen-Sheng Gao (Geochimica et Cosmochimica Acta, 2025)

The transformation from a macroscopic 1D light trapper to a 3D light trapper and the siphoning effect on the desalinating evaporator - Sen Ai; Yi-Nuo Wang; Jun-Shuai Li; Cheng-Yu He; Bao-Hua Liu; Gang Liu; Xiang-Hu Gao (Desalination, 2025)

Methane hydrate formation kinetics and structure information in the presence of cyclopentane under different reaction evolution - Wen-Zhe Sun; Hai-Long Liu; Kai Zhang; Xu-Ke Ruan; Yi-Song Yu; Xiao-Sen Li (Chemical Engineering Journal, 2025)

Structural characterizations and antiaging activities of hydrolyzed low-molecular-weight polysaccharides from Polygoni Multiflori Radix Praeparata - Wei Xu; Xue-Jian Li; Yu-Sen Zhong; Jia-Qi He; Wei Xie; You-Kun Kang; Hua-Zhong Ying; Chen-Huan Yu (Carbohydrate Polymers, 2025)

Inhibition of KDM6B prevents osteoarthritis by blocking growth plate-like H3K27me3 loss in bivalent genes - Hao Du; Yao Zhang; Xi Yu; Xuanhe You; Diwei Wu; Ze Du; Yongrui Cai; Zhenyu Luo; Hanpeng Lu; Zhixin Liao; Bi-Sen Ding; Ya Zhao; et al. (Science China Life Sciences, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

Density Effects on Mixing in Porous Media: Multi-dimensional Flow-Through Experiments and Model-Based Interpretation - Yu Ye; Sen Liu; Gabriele Chiogna; Chunhui Lu; Massimo Rolle (Transport in Porous Media, 2025)

Characterization of spatial and temporal evolution of carbon stock and multi-scenario prediction of Haba Lake Protected Area in Ningxia based on PLUS-InVEST model - Qikang Geng; Sen Hou; Dian Yu; Zhen Bian (Environmental Science and Pollution Research, 2025)

Seasonal variations and hydrological management regulate nutrient transport in cascade damming: Insights from carbon and nitrogen isotopes - Yujing Yang; Wanfa Wang; Shengde Yu; Yuanbi Yi; Sen Xu; Yuanzhi Yao; Jun Zhong; Wenhong Shi; Sainan Chen; Qixin Wu; Zuhong Ou; Hu Ding; et al. (Water Research, 2025)

Mixed vector autoregression and GARCH–Copula approach for long-term streamflow probabilistic forecasting in a multisite system - Saijin Ji; Bin Xu; Yu Sun; Ran Mo; Sen Wang; Peng Lu (Stochastic Environmental Research and Risk Assessment, 2025)

α-asarone activates mitophagy to relieve diabetic encephalopathy via inhibiting apoptosis and oxidative stress - Xiao-dan Yan; Rong-hua Fan; Yu Wang; Xiao-xu Duan; Xuan Wei; Lin-sen Li; Qing Yu (Metabolic Brain Disease, 2025)

Treg Upregulation by Treadmill Training Accelerates Myelin Repair Post-Ischemia - Juan Zhong; Tao Liu; Yingxi He; Ying Zhu; Sen Li; Yuan Liu; Ce Yang; Lehua Yu; Lu Pan; Ying Yin; Botao Tan (Journal of Neuroimmune Pharmacology, 2025)

Toxicity assessment of wastewater using a battery of bioassays in two textile wastewater treatment plants from a large industrial park in Guangxi, Southwest China - Feng-Jiao Peng; Sen Li; Wen-Dan You; Xin-Yu Wang; Xing-Jun Feng; Bin Yang; Guang-Guo Ying (Science of The Total Environment, 2025)

In-situ sulfur isotope characteristic and genesis of sedimentary pyrite with varying crystal morphologies in coal-bearing strata in North China - Lihui Liu; Sen Wang; Zhanjie Xu; Tianjiao Yu; Joan S. Esterle; Suzanne D. Golding; Yunfei Xi; Qinfu Liu (Sedimentary Geology, 2025)

Interfacial composition on the mechanical properties, microstructure and digestion of emulsion-filled whey protein gels: Effect of soy and whey protein ratios - Georgina Benewaa Yeboah; Sen Wang; Wei Wu; Haowei Zhang; Prince Ofori Donkor; Juan Wu; Yu Cheng (Food Bioscience, 2025)

Recent progress of high-performance interconnectors for SOFC: From materials, protective coatings, optimizing strategies, towards the real stack applications - Yingzhen Hu; Desheng Li; Hu Guo; Sen-Hui Liu; Yu Meng; Shujiang Ding; Cheng-Xin Li (Chemical Engineering Journal, 2025)

The relationship between serum coagulation parameters and the recurrence of chronic subdural hematoma - Zhen Bao; Sen Xu; Gang Cui; Jian-Min Qu; Tian-Yu Liang (Molecular and Cellular Biochemistry, 2025)

A sustainable process for Pb, Zn, and Fe from copper slag by salt roasting-magnetization roasting-magnetic separation - Xinze Gao; Yinhe Lin; Dong Guan; Zhaohua Liu; Bo Deng; Qingshan Du; Yanjun Liu; Sen Yu; Juncheng Li; Lingling Cao (Process Safety and Environmental Protection, 2025)

Effect of hot-air drying processing on the volatile organic compounds and maillard precursors of Dictyophora Rubrovalvata based on GC-IMS, HPLC and LC-MS - Lingshuai Meng; Yu Nie; Qingsong Zhou; Tingting Zheng; Jianxin Song; Chao Zhang; Haijiang Chen; Dong Lin; Sen Cao; Su Xu (Food Chemistry, 2025)

Echelon extraction of valuable components from salt lake brine substrate - Xiangting Tang; Jun Chen; Ye Zhang; Jianguo Yu; Sen Lin (Desalination, 2025)

Sedimentary Signatures of Super Typhoon Haiyan: Insight from Core Record in South China Sea - Yu-Huang Chen; Chih-Chieh Su; Pai-Sen Yu; Ta-Wei Hsu; Sheng-Ting Hsu; Hsing-Chien Juan; Yuan-Pin Chang; Yu-Fang Ma; Shye-Donq Chiu (Journal of Marine Science and Engineering, 2024)
Sedimentary records of event deposits are crucial for regional natural disaster risk assessments and hazard history reconstructions. After Super Typhoon Haiyan passed through the South China Sea in 2013, five gravity cores were collected along the typhoon path in the southern South China Sea basin (>3800 mbsl). The results showed that Super Typhoon Haiyan deposits with clear graded bedding are preserved at the top of all cores. The thickness of the typhoon layers ranges from 20 to 240 cm and is related to changes in typhoon intensity. The lack of river-connected submarine canyon systems limited the transportation of terrestrial sediments from land to sea. Super Typhoon Haiyan-induced large surface waves played an important role in carrying suspended sediment from the Philippines. The Mn-rich layers at the bottom of the typhoon layers may be related to the soil and rock composition of the Palawan region, which experienced tsunami-like storm surges caused by Super Typhoon Haiyan. These Mn-rich layers may serve as a proxy for sediment export from large-scale extreme terrigenous events. This study provides the first sedimentary record of extreme typhoon events in the deep ocean, which may shed light on reconstructing regional hazard history.

Melatonin reduces postharvest decay of blueberries by regulating ascorbate–glutathione cycle and membrane lipid metabolism - Sen Cao; Linxiang Qiao; Tianyu Huang; Yu Zhang; Guangfan Qu; Xiaohong Kou (Postharvest Biology and Technology, 2024)

Revealing the interplay of dissolved organic matters variation with microbial symbiotic network in lime-treated sludge landscaping - Zexu Chen; Yu Zhang; Boyuan Yang; Sen Fan; Lanfeng Li; Peng Yang; Weijun Zhang (Environmental Research, 2024)

N-acetylcysteine mitigates oxidative damage to the ovary in D-galactose-induced ovarian failure in rabbits - Yu Xue; Huafeng Bian; Shaocheng Bai; Zhiyuan Bao; Lei Wang; Sen Wang; Bohao Zhao; Xinsheng Wu; Yang Chen (Molecular Biology Reports, 2024)

Stomatin-like protein 2 promotes cell proliferation and survival under 5-Fluorouracil stress in hepatocellular carcinoma - Xiaoqi Li; Yahui Zheng; Kangkang Yu; Sen Hou; Huxiao Cui; Ruiqi Yin; Yu Zhou; Qingfeng Sun; Jubo Zhang; Chong Huang (Molecular Biology Reports, 2024)

Effects of Different Nitrogen Fertilizer Rates on Soil Magnesium Leaching in Tea Garden - Sen Wang; Wei Lin; Qi Ye; Wenzhuo Lv; Penghui Liao; Jinhui Yu; Cong Mu; LiangQuan Wu; Muhammad Atif Muneer; Yinjie Zhang; Runzhi Zhan; Aolin Wu; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Contributions of the bacterial communities to the microcystin degradation and nutrient transformations during aerobic composting of algal sludge - Hainan Wu; Jiahui Zhou; Sen Zhang; Yu Gao; Chengkai Wang; Haibing Cong; Shaoyuan Feng (Journal of Environmental Management, 2024)

Experimental studies and pore-scale modeling of hydrate dissociation kinetics at different depressurization rates in a cubic hydrate simulator - Chang-Wen Xiao; Xiao-Sen Li; Hong-Feng Lu; Gang Li; Chen-Lu Xu; Rong-Rong Qi; Dong-Hui Xing; Xian Li; Yi-Fan Weng; Lu Yu (Chemical Engineering Journal, 2024)

Exploring the remarkable effects of microwave treatment on starch modification: From structural evolution to changed physicochemical and digestive properties - Mengdi Cai; Yu Zhang; Hongwei Cao; Sen Li; Ying Zhang; Kai Huang; Hongdong Song; Xiao Guan (Carbohydrate Polymers, 2024)

Health benefits of saponins and its mechanisms: perspectives from absorption, metabolism, and interaction with gut - Yu Zhang; Ruojie Hao; Junda Chen; Sen Li; Kai Huang; Hongwei Cao; Mohamed A. Farag; Maurizio Battino; Maria Daglia; Esra Capanoglu; Fan Zhang; Qiqi Sun; et al. (Critical Reviews in Food Science and Nutrition, 2024)

MeJA enhances antioxidant activity and reduces membrane lipid degradation by maintaining energy charge levels in crystal grapes - Donglan Luo; Tianyu Huang; Xiaohong Kou; Yu Zhang; Liangjie Ba; Xiufen Wang; Sen Cao (Postharvest Biology and Technology, 2024)

Bimetallic MIL-68(InFe) MOF nanorods for biomimetic photocatalytic N2 fixation - Cheng Liu; Mengning Chen; Yueling Chen; Qi Chen; Jionghua Wu; Sen Lin; Ling Wu; Jimmy C. Yu (Chemical Engineering Journal, 2024)

Effects of Volcanic Activity on Organic Matter Sources and the Paleoenvironment: Geochemical Evidence from Upper Carboniferous Source Rocks (Batamayineishan Formation) in Eastern Junggar, NW China - Ming Shao; Tianzhu Lei; Shuncun Zhang; Shengyin Zhang; Yu Pei; Sen Song (Journal of Earth Science, 2024)

Genetic diversity of Dotilla myctiroides (Crustacea: Brachyura: Dotillidae) based on mitochondrial cox 1 gene marker in Peninsular Malaysia - Sze-Looi Song; Yu-Quan Toh; Hoi-Sen Yong; Zheng-Xian Lew; Ye-Ian Chang (Marine Biology Research, 2024)

Active longevity and aging: dissecting the impacts of physical and sedentary behaviors on longevity and age acceleration - Ting Yu Lu; Jiao Wang; Chao Qiang Jiang; Ya Li Jin; Kar Keung Cheng; Tai Hing Lam; Wei Sen Zhang; Lin Xu (GeroScience, 2024)
Background To examine the associations of physical activity (PA) and sedentary behavior (SB) with longevity and age acceleration (AA) using observational and Mendelian randomization (MR) studies, and quantify the mediating effects of lipids. Methods In Guangzhou Biobank Cohort Study (GBCS), PA and SB were assessed by the Chinese Version of the International Physical Activity Questionnaire. Longevity was defined as participants whose age at follow-up or at death was at or above the 90th age percentile. AA was defined as the residual resulting from a linear model that regressed phenotypic age against chronological age. Linear regression and Poisson regression with robust error variance were used to assess the associations of total and specific PA in different intensities, and SB with AA and longevity, yielding βs or relative risks (RRs) and 95% confidence intervals (CIs). Two-sample MR was conducted to examine the causal effects. Mediation analysis was used to assess the mediating effects of lipids. Results Of 20,924 participants aged 50 + years in GBCS, during an average follow-up of 15.0 years, compared with low PA, moderate and high PA were associated with higher likelihood of longevity (RR (95% CI): 1.56 (1.16, 2.11), 1.66 (1.24, 2.21), respectively), and also cross-sectionally associated with lower AA (β (95% CI): -1.43 (-2.41, -0.45), -2.09 (-3.06, -1.11) years, respectively). Higher levels of moderate PA (MPA) were associated with higher likelihood of longevity and lower AA, whereas vigorous PA (VPA) showed opposite effects. The association of PA with longevity observed in GBCS was mediated by low-density lipoprotein cholesterol (LDL-C) by 8.23% (95% CI: 3.58–39.61%), while the association with AA was mediated through LDL-C, triglycerides and total cholesterol by 5.13% (3.94–7.30%), 7.81% (5.98–11.17%), and 3.37% (2.59–4.80%), respectively. Additionally, in two-sample MR, SB was positively associated with AA (β (95% CI): 1.02 (0.67, 1.36) years). Conclusions PA showed protective effects on longevity and AA, with the effects being partly mediated through lipids. Conversely, SB had a detrimental impact on AA. MPA was associated with higher likelihood of longevity and reduced AA, whereas VPA showed adverse effects. Our findings reinforce the recommendation of “sit less and move more” to promote healthy longevity, and highlight the potential risks associated with VPA in the elderly.

Volatomic differences among Vitis amurensis cultivars and its hybrids with V. vinifera revealed the effects of genotype, region, and vintage on grape aroma - Ming-Yu Li; Xuan-Xuan Pei; Ning Shi; Yi-Ming Yang; Shu-Tian Fan; Yan-Feng Sun; Qing-Sen Kong; Chang-Qing Duan; Keji Yu; Jun Wang (Food Research International, 2024)

Degradation of sulfamethazine in coastal aquaculture tailwater by Na2S2O4@iron-electrode electrooxidation combined with ceramic membrane process - Wei Song; Yuning Fang; Hongze Fang; Deming Gu; Xing Du; Sen Xu; Caixia Fu; Yu Zhou; Zhihong Wang (Environmental Pollution, 2024)

No increase of soil wind erosion with the establishment of center pivot irrigation system in Mu-Us sandy land - Jie Liao; Fei Peng; Wenping Kang; Xiaojie Chen; Jianbo Sun; Ben Chen; Yu Xia; Heqiang Du; Sen Li; Xiang Song; Tao Wang (Science of The Total Environment, 2024)

Experimental and numerical simulation research on the transport process of bubble clusters in aeration system - Sen Han; Zhao Duan; Yu Li (Journal of Environmental Management, 2024)

Dehydration of collagen hydrogel simply by immersion in sodium carboxymethylcellulose solution - Jingmin Wu; Zhe Yu; Yuxin Ma; Kaidi Zhu; Jian Li; Bor-Sen Chiou; Fang Zhong; Fei Liu (Food Hydrocolloids, 2024)

Valuable components recovery from wastewater and brine using electrocoagulation-based coupled process: A systematic review - Ye Zhang; Xiangting Tang; Jiayi Zhang; Yi Zhang; Ruoning Yu; Wenshuo Wang; Sen Lin; Jianguo Yu (Desalination, 2024)

Enhancing lithium extraction from low grade salt lake brines using high powder loading aluminum-based adsorbent granules - Yanan Pan; Ye Zhang; Haiping Su; Jianguo Yu; Sen Lin (Desalination, 2024)

Low-humidity sensor and biomimetic power supply based on mesoporous silica/polymerizable deep eutectic solvent ionogels - Zhiyan Ma; Yanyu Cui; Yaping Song; Yunlong Yu; Hongran Zhao; Sen Liu; Xishuang Liang; Teng Fei; Tong Zhang (Chemical Engineering Journal, 2024)

Abnormal Innervation, Demyelination, and Degeneration of Spiral Ganglion Neurons as Well as Disruption of Heminodes are Involved in the Onset of Deafness in Cx26 Null Mice - Yue Qiu; Le Xie; Xiaohui Wang; Kai Xu; Xue Bai; Sen Chen; Yu Sun (Neuroscience Bulletin, 2024)

Correction to: The relationship between serum coagulation parameters and the recurrence of chronic subdural hematoma - Zhen Bao; Sen Xu; Gang Cui; Jian-Min Qu; Tian-Yu Liang (Molecular and Cellular Biochemistry, 2024)

Circ_0003789 Knockdown Inhibits Tumor Progression by miR-429/ZFP36L2 Axis in Gastric Cancer - Lu Wan; Yu Jia; Na Chen; Sen Zheng (Biochemical Genetics, 2024)

In-situ electrochemical study on the effects of Fe(III) on kinetics of pyrite acidic pressure oxidation - Yu Zhang; Can Cui; Sen Lin; Heping Li; Lian Yang; Yadian Xie; Hailiang Hu; Lingyun Zhou; Huanjiang Wang; Chunyan Li (Acta Geochimica, 2024)

Analysis on dust prevention law of new barrier strategy in fully mechanized coal mining face - Junwei Zhao; Haiming Yu; Hui Dong; Sen Xie; Yu Cheng; Zongwei Xia (Process Safety and Environmental Protection, 2024)

Neoproterozoic (ca. 830 Ma) carbonatite dykes from Qianlishan in the western North China Craton: Petrogenesis and metallogenic implications - Hong-Yu Wang; Shuan-Hong Zhang; Ling-Hao Kong; Jun-Ling Pei; Yue Zhao; Qi-Qi Zhang; Sen Wang; Guo-Hui Hu (Precambrian Research, 2024)

Biochar reduces antibiotic transport by altering soil hydrology and enhancing antibiotic sorption - Xiang-Yu Tang; Wen-Min Yin; Guang Yang; Jun-Fang Cui; Jian-Hua Cheng; Fei Yang; Xiao-Yu Li; Chun-Yan Wu; Sen-Gen Zhu (Journal of Hazardous Materials, 2024)

Photochemical enrichment of dissolved organic matter from different soils of a tidal river basin: significance to estuarine carbon cycle - Yuping Zhou; Yuxuan Zhu; Sen Jiang; Di Meng; Yu Pang; Yihua Xiao (Frontiers in Marine Science, 2024)
Eroded soils sustain a substantial part of organic matter in tidal rivers adjacent to estuaries, and photochemical transformations of soils in tidal rivers would influence estuarine elemental cycles. However, complex aquatic environments and diverse soil sources complicate the enrichment of dissolved organic matter (DOM) photoreleased from soils. Here, we conducted a 7-day irradiation experiment for seven kinds of soils from the lower basin of Dagu River (DGR) in the laboratory to study the influence of salinity and soil properties on DOM chemistry by characterizing the content and optical properties of DOM. Results showed that light cultures had higher amount of DOM and humic-like components than dark cultures. Principal component analysis (PCA) and Mantel’s analysis found that salinity and soil properties significantly influence the production of photoreleased DOM, especially humic-like components. Salinity could inhibit the photodissolution of soils, and aged soils with low δ 13 C SOM released more DOM and humic-like components. Although the DGR is impacted by intruded seawater, high content of photoreleased DOM in seawater cultures still pointed out the important contribution of soil photodissolution to the DOM reservoir of tidal rivers. Considering high proportion of humic-like components in photoreleased DOM, photochemical transformations of soils in tidal rivers would promote the export flux of carbon from estuaries to open seas. This study emphasizes the importance of soil photodissolution of tidal rivers in the carbon transfer from lands to oceans.

Simultaneous characterization and quantification of 25 flavonoid compounds in Actinidia arguta Miq. leaves by HPLC-DAD and screening for their inhibitory activity on α‑glucosidase - Yu-Fei Hou; Lu Bai; Shao-Jing Liu; Sen Guo; Ya-Long Wang; Chi-Tang Ho; Nai-Sheng Bai (Phytochemistry Letters, 2024)

Large-scale soil application of hydrochar: Reducing its polycyclic aromatic hydrocarbon content and toxicity by heating - Hongyu Si; Rui Wang; Yuqing Zhao; Han Hao; Changkai Zhao; Sen Xing; Hewei Yu; Xiaohui Liang; JiKai Lu; Xiuxiu Chen; Bing Wang (Journal of Hazardous Materials, 2024)

Single-Cell Sequencing Technology and Its Application in the Study of Central Nervous System Diseases - Yang Ding; Yu-Yuan Peng; Sen Li; Can Tang; Jie Gao; Hai-Yan Wang; Zai-Yun Long; Xiu-Min Lu; Yong-Tang Wang (Cell Biochemistry and Biophysics, 2024)

The formation mechanism, analysis strategies and regulation measures of cereal aroma: A review - Yao Feng; Hongwei Cao; Hongdong Song; Kai Huang; Yu Zhang; Ying Zhang; Sen Li; Yingjie Li; Jun Lu; Xiao Guan (Trends in Food Science & Technology, 2024)

Novel method for identifying the heaviest QED atom - Jing-Hang Fu; Sen Jia; Xing-Yu Zhou; Yu-Jie Zhang; Cheng-Ping Shen; Chang-Zheng Yuan (Science Bulletin, 2024)

Quantum spin driven Yu-Shiba-Rusinov multiplets and fermion-parity-preserving phase transition in K3C60 - Shu-Ze Wang; Xue-Qing Yu; Li-Xuan Wei; Li Wang; Qiang-Jun Cheng; Kun Peng; Fang-Jun Cheng; Yu Liu; Fang-Sen Li; Xu-Cun Ma; Qi-Kun Xue; Can-Li Song (Science Bulletin, 2024)

Study on bubble collapse mechanism in aeration system based on venturi cavitation effect - Sen Han; Yaxin Huang; Tinglin Huang; Yu Li (Process Safety and Environmental Protection, 2024)

Effect of cations on monochlorobenzene adsorption onto bentonite at the coexistence of Tween 80 - Changzhong Xu; Yu Ning; Changxiang Wang; Sen Yang; Zhe Yang; Yilian Li (Journal of Hazardous Materials, 2024)

Sodium carboxymethyl cellulose as a stabilizer for fabricating mineralized collagen films with improved wet mechanical properties - Kaidi Zhu; Zhe Yu; Jian Li; Bor-Sen Chiou; Maoshen Chen; Fang Zhong; Fei Liu (Food Hydrocolloids, 2024)

Maize cultivar mixtures increase aboveground biomass and grain quality via trait dissimilarity and plasticity - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (European Journal of Agronomy, 2024)

Black kitchen waste based solar evaporator employing radiative cooling film as difffuse substrate for efficient desalination - Sen Ai; Yi-Nuo Wang; Tong-Jun Li; Yong-Zhi Chen; Cheng-Yu He; Bao-Hua Liu; Gang Liu; Xiang-Hu Gao (Desalination, 2024)

Adsorption behavior and the potential risk of As(V) in soils: exploring the effects of representative surfactants - Zhi Feng; Yu Ning; Sen Yang; Zhe Yang; Changxiang Wang; Yilian Li (Environmental Monitoring and Assessment, 2024)

Comparative transcriptome analysis reveals immune-related genes involved in allograft and xenograft transplantation in Pinctada fucata - Yusi Zheng; Pei Wang; Ying Guo; Lirong Bai; Dahui Yu; Sen Zhao (Frontiers in Marine Science, 2024)
Background The marine pearl culture industry is a key industry in the Beibu Gulf of China that achieves large-scale pearl production by artificial nucleus insertion in pearls. High-quality pearls can produced by xenotransplantation, but allotransplantation or xenotransplantation can lead to various immune responses, resulting in nucleus rejection or even the recipient shell death and thereby causing significant losses in pearl production. Methods Few studies have investigated the immune defenses of oysters related to allografts and xenografts. In this study, transcriptomic comparisons of allograft and xenograft Pinctada fucata haemocytes were conducted to identify genes associated with immune responses. Results A total of 33.11 Gbp of clean reads were generated from five P. fucata haemocytes. De-novo assembly of quality-filtered reads generated a total of 26,526 unigenes, with 22,002 known genes and 4,524 predicted novel genes. In addition, 34,904 novel transcripts were detected, with 15,620 novel alternative splicing isoforms of known protein coding genes and 4,605 belonging to novel protein coding genes, with the remaining 14,679 comprising long non-coding RNA transcripts. Functional enrichment analysis of immune-related differentially expressed genes (DEGs) using the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases revealed 36–44 significantly enriched GO terms and 34 significantly enriched KEGG pathways. Ten DEGs were subjected to validation of expression levels using RT-q PCR analysis, revealing generally consistent values as the high-throughput sequencing data. Conclusion Oyster haemocytes were comprehensively evaluated in this study using transcriptomic comparisons and with a focus on immune-related functional genes and pathways. The results revealed numerous DEGs related to immune function that can serve as the basis for subsequent immune response analysis of allotransplantation and xenotransplantation.

Review of the research status on the transmission and diffusion characteristics of indoor viral aerosol particles - Yaxin Huang; Jie Wan; Sen Han; Yu Li (Environmental Science and Pollution Research, 2024)

Comparative proteomics reveal the humoral immune rejection of pearl oyster Pinctada fucata to xenograft from Pinctada maxima - Pei Wang; Ying Guo; Suping Li; Yusi Zheng; Tao Li; Sen Zhao; Dahui Yu; Lirong Bai (Aquaculture, 2024)

New design to enhance phosphonate selective removal from water by MOF confined in hyper-cross-linked resin - Shuangli Li; Yu Zhang; Shuo Zhao; Liying Zhang; Sen Qiao; Jiti Zhou (Science of The Total Environment, 2024)

Research on the dust reduction by spraying law of fully mechanized face using a large-scale dust and droplet coupling model - Yuxi Ye; Haiming Yu; Sen Xie; Hui Dong; Weimin Cheng; Xingjie Wang (Process Safety and Environmental Protection, 2024)

Transcrustal magmatic processes of the Tianshuigou dolerite sill from the ca. 1.32 Ga Yanliao large igneous province: Insights from zoned plagioclase macrocrysts - Ling-Hao Kong; Shuan-Hong Zhang; Hong-Yu Wang; Sen Wang; Yu-Hang Cai; Qi-Qi Zhang; Yue Zhao; Guo-Hui Hu (Lithos, 2024)

Enzymatic hydrolysis of oat core flour improves physiochemical and sensory behaviors for oat milk - Min Zhang; Kai Huang; Jun Lu; Anni Lu; Xiao Guan; Yu Zhang; Sen Li; Hongdong Song; Hongwei Cao; Zhu Sun; Zhiquan Yu (Journal of Cereal Science, 2024)

Enhancing methanol oxidation electrocatalysis by Pt/Mo2CT -rGO ternary hybrid catalyst - Ruige Wang; Xin Zhang; Sijie Chang; Sen Jin; Junkai Wang; Chaofan Wang; Yukai Chang; Zhipeng Yu; Qianku Hu; Aiguo Zhou (Fuel, 2024)

Peroxymonosulfate activation by walnut shell activated carbon supported nano zero-valent iron for the degradation of tetracycline: Performance, degradation pathway and mechanism - Pingping Duan; Fanlong Kong; Xiuzheng Fu; Zhijie Han; Guangwei Sun; Zhengda Yu; Sen Wang; Yuqian Cui (Environmental Research, 2024)

Mechanism of propylene effect on the NH3-SCR performance of Cu-SSZ-13 catalyst - Wenqing Ding; Yu Sun; Jingjing Liu; Sen Xue; Xuewang Han; Zidi Yan; Yunbo Yu; Yulong Shan; Hong He (Chemical Engineering Journal, 2024)

Rapid prediction of regenerator performance for regenerative cryogenics cryocooler based on convolutional neural network - Xiantong Chen; Shanshan Li; Jun Yu; Sen Yang; Hao Chen (International Journal of Refrigeration, 2024)

Kinetic studies of the secondary hydrate formation in porous media based on experiments in a cubic hydrate simulator and a new kinetic model - Chang-Wen Xiao; Xiao-Sen Li; Gang Li; Yi-Song Yu; Qiu-Nan Lv; Yang Yu; Yi-Fan Weng; Jian-Wu Liu; Jian-Xing Yu (Fuel, 2024)

Unravelling the synergistic effect of incorporation of β-glucan and high intensity ultrasound treatment on the stability of highland barley milk - Hongwei Cao; Ranqing Li; Sen Li; Hongdong Song; Kai Huang; Yu Zhang; Jun Lu; Xiao Guan (Food Hydrocolloids, 2024)

Triclocarban exhibits higher adipogenic activity than triclosan through peroxisome proliferator-activated receptors pathways - Jia-Da Zhang; Sen He; Ting-Ting He; Chuan-Hai Li; Bing-Hua Yan; Yuan Yang; Jian Yang; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Environmental Pollution, 2024)

Desorption enhancement of aluminum-based adsorbent in lithium extraction from sulfate-type salt lakes - Yihong Guo; Jianguo Yu; Haiping Su; Sen Lin (Desalination, 2024)

Reciprocal transplant experiment reveals multiple factors influencing changes in coral microbial communities across climate zones - Ya-Fan Chan; Yu-Hsiang Chen; Sheng-Ping Yu; Hsing-Ju Chen; Yoko Nozawa; Sen-Lin Tang (Science of The Total Environment, 2024)

Kinetics studies of methane hydrate formation and dissociation in the presence of cyclopentane - Yi-Song Yu; Wen-Zhe Sun; Chang Chen; Xiao-Sen Li; Zhao-Yang Chen (Fuel, 2024)

Study on the transport and deposition of micron-sized particles with different densities in the coal mine environment in miners - Yu Cheng; Haiming Yu; Yuxi Ye; Yao Xie; Junwei Zhao; Sen Xie (Fuel, 2024)

High-performance lithium metal batteries enabled by a nano-sized garnet solid-state electrolyte modified separator - Kai Yu; Huipeng Zeng; Jun Ma; Yidong Jiang; Huiyun Li; Ludan Zhang; Qiangqiang Zhang; Xuyi Shan; Tingting Li; Xiaoqi Wu; Hongli Xu; Wei Huang; et al. (Chemical Engineering Journal, 2024)

Model of shrimp pond-mediated spatiotemporal dynamic distribution of antibiotic resistance genes in the mangrove habitat of a subtropical gulf - Yimeng Sang; Shuming Mo; Sen Zeng; Xiaoling Wu; Muhammad Kashif; Jingjing Song; Dahui Yu; Lirong Bai; Chengjian Jiang (Science of The Total Environment, 2023)

Long-term fencing can't benefit plant and microbial network stability of alpine meadow and alpine steppe in Three-River-Source National Park - Keyu Chen; Sen Xing; Hailan Shi; Yu Tang; Mingxin Yang; Qiang Gu; Yaoming Li; Jing Zhang; Baoming Ji (Science of The Total Environment, 2023)

Ascendancy of pyraclostrobin nanocapsule formulation against Rhizoctonia solani: From a perspective of fungus - Li Ma; Meng Yu; Yingjian Ma; Linying Gao; Shouhe Pan; Xuefeng Li; Xuemin Wu; Yong Xu; Sen Pang; Ping Wang (Pesticide Biochemistry and Physiology, 2023)

pH-responsive ZIF-8 film-coated mesoporous silica nanoparticles for clean, targeted delivery of fungicide and environmental hazard reduction - Yingjian Ma; Yinmin Wang; Rui Zhao; Zhijie Wang; Shuang Li; Meng Yu; Sen Pang; Xinyu Guo; Yong Xu; Xuemin Wu (Journal of Environmental Chemical Engineering, 2023)

Metastable structure II methane hydrate: A bridge to obtain high methane uptake in the presence of thermodynamic promoter - Yi-Song Yu; Xiao-Sen Li (Chemical Engineering Journal, 2023)

Multidimensional risk spillover among power, coal, and carbon markets: empirical evidence from China - Jian Tang; Zheng Yu Ren; Hsing Hung Chen; Sen Qiao (Environmental Science and Pollution Research, 2023)

Numerical Simulation Study on Heat Transfer Performance of Middle-deep U-bend Geothermal Well - Ling-Ling Bao; Jun-Yan Li; Hai-Ming Guo; Guo-Qing Niu; Zhe Wang; Yao Zhang; Yu-Sen Wang (Applied Geophysics, 2023)

Improved functionality and safety of peptides by the formation of peptide-polyphenol complexes - Duanquan Lin; Le-Chang Sun; Wei-Sen Huo; Ling-Jing Zhang; Yu-Lei Chen; Song Miao; Min-Jie Cao (Trends in Food Science & Technology, 2023)

Effect of aggregation behavior on microplastic removal by magnetic Fe3O4 nanoparticles - Ruiqi Yan; Sen Lin; Weinan Jiang; Xia Yu; Lei Zhang; Wentao Zhao; Qian Sui (Science of The Total Environment, 2023)

Alkaline amino acids present unique aggregation behavior for quinoa protein gelation under microwave irradiation - Hongwei Cao; Xiaoxue Wang; Yuxin Ruan; Kai Huang; Yu Zhang; Hongdong Song; Sen Li; Xiao Guan (Food Hydrocolloids, 2023)

Characterization of atmospheric mercury from mercury-added product manufacturing using passive air samplers - Qing Luo; Yuxuan Ren; Zehang Sun; Yu Li; Bing Li; Sen Yang; Wanpeng Zhang; Frank Wania; Yuanan Hu; Hefa Cheng (Environmental Pollution, 2023)

Lithium extraction process from low grade Na+/K+ brines dependent on high layer charge layered double hydroxides - Bingchun Sheng; Haiping Su; Jianguo Yu; Sen Lin (Desalination, 2023)

Interaction of chromium-sulfur-iron during Cr(VI) stabilization by polysulfide-modified nanoscale zero-valent iron for groundwater remediation: Batch experiments and numerical simulation - Jinhao Yu; Sen Yang; Danqing Liu; Zhe Yang; Jiali Xu; Yilian Li; Zhi Tang (Chemical Engineering Journal, 2023)

Trends and drivers of soil multifunctionality along elevation gradients in the Altun Shan drylands of China - Shi-hang Zhang; Yu-sen Chen; Yong-xing Lu; Hao Guo; Xing Guo; Xiao-bing Zhou; Yuan-ming Zhang (Journal of Mountain Science, 2023)

Current status and future challenges of chlorobenzenes pollution in soil and groundwater (CBsPSG) in the twenty-first century: a bibliometric analysis - Zhi Feng; Zhe Yang; Sen Yang; Hanxiang Xiong; Yu Ning; Changxiang Wang; Yilian Li (Environmental Science and Pollution Research, 2023)

Applicability of photovoltaic panel rainwater harvesting system in improving water-energy-food nexus performance in semi-arid areas - Weiyi Ye; Enpu Ma; Liuwen Liao; Yi'an Hui; Shiyu Liang; Yiwen Ji; Sen Yu (Science of The Total Environment, 2023)

Nitrogen removal performance and microbial community of a novel combined electrochemical biofilter for treating a mixture of raw sewage and secondary effluent - Yongqing Niu; Hui Zhang; Sen Yang; Bingyan Liu; Ziyao Hao; Luji Yu; Zhaoxu Peng (Journal of Water Process Engineering, 2023)

Evaluating the impact of the humic acid amendment on antibiotic resistance genes reduction and product quality during swine manure composting - Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Shan-Shan Sun; Xi Yang; Yu-Sen Luo; Ayodeji Bello; Taha Ahmed Mohamed; Rong-Jie Ren; Wan-Ting Li; Rashid Mohamed Ahmed; Rui-Long Wang (Journal of Environmental Chemical Engineering, 2023)

Well-oriented immobilized immunoaffinity magnetic beads for detection of fumonisins in grains and feeds via pre-column automatic derivatization of high-performance liquid chromatography - Jinnan Chen; Meng Wang; Sen Li; Jin Ye; Li Li; Yu Wu; Di Cai; Tongtong Liu; Lin Zhu; Yi Shao; Songxue Wang (Food Chemistry, 2023)

Trade-offs and synergies of plant traits co-drive efficient nitrogen use in intercropping systems - Hao Yang; Wei-Ping Zhang; Hua-Sen Xu; Rui-Peng Yu; Ye Su; Surigaoge Surigaoge; Pei-Xuan Wang; Xin Yang; Hans Lambers; Long Li (Field Crops Research, 2023)

Crop cultivar mixtures stabilize productivity, partly via facilitation, when conditions are less benign - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Jian-Hao Sun; Jian-Hua Zhao; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (Field Crops Research, 2023)

A dye-based desalinating evaporator independent on solar absorber of excellent optical properties for efficient desalination - Sen Ai; Yi-Nuo Wang; Tong-Jun Li; Yong-Zhi Chen; Cheng-Yu He; Bao-Hua Liu; Gang Liu; Xiang-Hu Gao (Desalination, 2023)

Insight into intermediate impact of aging acidity and regulating mechanism on the performance of LiFePO4/C cathode material - Ting Zhang; Jianguo Yu; Sen Lin (Chemical Engineering Journal, 2023)

Coating TiO2 with MIL-101(Fe) to decarboxylate D-Glu and D-MeAsp of microcystin-LR from HA-rich water: Diminishing the inhibitory effect of humic acids - Yarui Wang; Chengzhuo Yu; Sen Wang; Jin Xu; Fanglan Geng; Silong Wang; Jitao Lv; Lixia Zhao; Yawei Wang (Chemical Engineering Journal, 2023)

Preemptive QP001, a fast-acting meloxicam formulation, provides analgesia and reduces opioid consumption following abdominal surgery: a randomized controlled trial - Yingyong Zhou; Bin Wang; Kaiming Duan; Zhihong Bai; Xianwen Hu; Mingjun Xu; Xiaohong Li; Yuanli Gao; Jiangang Li; Mengchang Yang; Ying Zhang; Wei Zhang; et al. (Inflammopharmacology, 2023)

Which molecular marker is better? Comparative analyses of COI and ITS2 in molecular identification of Trichogramma (Hymenoptera: Trichogrammatidae) - Ao-Kai Wang; Fang-Yi Li; De-Sen Wang; Yu-Rong He; Yuan-Xi Li; Zhi-Chao Yan (BioControl, 2023)

Application of water-saving irrigation and biostimulants on the agronomic performance of maize (Zea mays) - Cheng-Hsuan Chen; Kuan-Hung Lin; Yu-Sen Chang; Yu-Jie Chang (Process Safety and Environmental Protection, 2023)

From arc accretion to within-plate extension: Geochronology and geochemistry of the Neoproterozoic magmatism on the northern margin of the Yangtze Block - Yu Huang; Xiao-Lei Wang; Jun-Yong Li; Ru-Cao Li; De-Hong Du; Chang-Hong Jiang; Lin-Sen Li; Ning Ding (Precambrian Research, 2023)

Study on the effect of bubble number on the collapse of a multi-bubble system near the rigid wall - Sen Han; Yaxin Huang; Wenwei Fan; Qiyan Wang; Tinglin Huang; Yu Li (Ocean Engineering, 2023)

A high-yield and high-efficiency cultivation pattern of winter wheat in North China Plain: High-low seedbed cultivation - Zhuanyun Si; Junming Liu; Lifeng Wu; Sen Li; Guangshuai Wang; Jiachuan Yu; Yang Gao; Aiwang Duan (Field Crops Research, 2023)

Au loaded mesoporous SiO2/gelatin hydrogel: Detecting low humidity and NH3 - Zhiyan Ma; Yunlong Yu; Ke Wu; Yaping Song; Sen Liu; Xi Yang; Teng Fei; Tong Zhang (Chemical Engineering Journal, 2023)

Experimental study on PSPC beam – Concrete encased CFST column frame installed with novel steel panel dampers - Yu Lin; Yifei Wang; Wuhong Wu; Sen Yang; Zhengxing Guo; Dongzhi Guan; Guojian Li (Engineering Structures, 2023)

Source analysis of metals in the tea plant using linear correlation analysis combined with a lead-strontium isotope tracer - Yan Cong; Rui-lian Yu; Yu Yan; Bo-sen Weng; Gong-ren Hu; Jing-wei Sun; Jian-yong Cui; YanYan; Yao-yi Huang (CATENA, 2023)

Nε-(1-Carboxymethyl)-L-lysine, an advanced glycation end product, exerts malignancy on chondrosarcoma via the activation of cancer stemness - Ting-Yu Chang; Kuo-Cheng Lan; Chia-Hung Wu; Meei-Ling Sheu; Rong-Sen Yang; Shing-Hwa Liu (Archives of Toxicology, 2023)

Analysis of Flow and Runner Dynamic Response Characteristics under Pump Conditions of Variable-Speed Pump Turbine - Linmin Shang; Jingwei Cao; Lei Wang; Shuang Yu; Sen Ding; Zichao Wei; Zhengwei Wang; Xiaobing Liu (Journal of Marine Science and Engineering, 2023)
Pumped storage power stations can ensure the safe operation of the grid, as well as utilize clean energy sources to establish a low-carbon, safe, and efficient energy system. As pump turbines, the core components of pumped storage power plants, become more and more popular, the technical requirements for hydraulic design begin to improve year by year. However, when the unit operates far beyond the optimal range, the variable-speed pump turbine can overcome the shortcomings of the fixed-speed unit and solve the problem of unstable operation under partial load. The pressure pulsation of the unit in the pump condition is investigated by numerical simulation, analyzing the hydraulic thrust, and studying the dynamic response characteristics of the runner at a maximum speed of 456.5 rpm. Comparing the pressure pulsation amplitude of various components in the entire flow passage, the highest values of pressure pulsation were found in the runner and vaneless space. The axial hydraulic thrust has a fluctuation range between 174t and 198t and 0t to 40t for radial force. As per the structural analysis, it has been observed that the runner demonstrates uneven patterns in both its axial and radial deformations, with deformation mainly concentrated in radial displacement and stress distribution mainly concentrated on the blades near the crown. The dynamic stress amplitude of the runner at monitoring point S1 (located on the runner blade near the crown) is 37 MPa. This stress has a dominant frequency of 4.8fn, while the monitoring point S2 (located on the runner blade near the band) is 4 MPa, and the dominant frequency is 1.8fn. Using these findings, the design of the variable-speed pump turbine’s runner can be optimized, and the unit’s stable and secure operation can be guided accordingly.

Culturing reef-building corals on a laboratory dish: a simple experimental platform for stony corals - Shinya Shikina; Tzu-Chieh Lin; Yu-Ling Chu; Yin-Chu Cheng; Yu-En Chang; Naohisa Wada; Sen-Lin Tang; Yoshiyuki Iizuka; Yi-Ling Chiu (Frontiers in Marine Science, 2023)
Development and maintenance of coral reef ecosystems rely on daily micro-biological activities of healthy corals. Although a comprehensive understanding of coral biological properties, as well as factors negatively affecting coral growth, are essential to conserve existing corals, the current lack of a tractable culture and experimental platform has delayed acquisition of such knowledge. Here we show a highly versatile culture system, “coral-on-a-laboratory dish” (CLD), allowing long-term culturing of various corals in plastic/glass Petri dishes with maintenance of their biological properties. Under optimized conditions, coral microcolonies (~5 mm x 5 mm fragments) of Pocillopora damicornis were cultured for several months in dishes with high survivorship and characteristic growth. These microcolonies maintained their biological properties, such as reproduction, skeleton formation, coral-algal symbiosis, ingestion, and digestion. Thus far, CLD has been used to maintain at least 4 other coral species from 4 other families, including the Acroporidae, the Pocilloporidae, the Poritidae, and the Merulinidae for more than 2 months with 100% survivorship. CLD is applicable to a variety of biophysiological studies, including coral-algal symbiosis and impact assessment of marine pollutants, e.g., a sunscreen substance, oxybenzone, and an organic biocide, Irgarol 1051, at cellular-level resolution. The CLD platform, which allows easy and inexpensive coral maintenance in a laboratory incubator, represents a technological breakthrough that will greatly advance coral studies.

A powerful helper of azoxystrobin degradation—the unique mechanism of UGT72E2 promoting environmental degradation of azoxystrobin - Yu Wang; Jie Wu; Lingling Zhao; Wei Sun; Sen Yan; Sinuo Tian; Qiao Zhao; Wentao Zhu (Environmental Science and Pollution Research, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Graphene nano zinc oxide reduces the expression and release of antibiotic resistance-related genes and virulence factors in animal manure - Haibo Zhang; Weikun Guan; Jun Shu; Sen Yu; Yingmin Xiong; Gao Liu; Yuhong Zhong; Jia Chen; Zhigang Zhao; Ning He; Qingfeng Xing; Dongsheng Guo; et al. (Science of The Total Environment, 2023)

A self-intensified inverted evaporation model constructed by high entropy spectrally selective absorber coating (SSAC) for brine water concentration - Sen Ai; Yi-Nuo Wang; Tong-Jun Li; Yong-Zhi Chen; Cheng-Yu He; Bao-Hua Liu; Gang Liu; Xiang-Hu Gao (Journal of Water Process Engineering, 2023)

Green water-etching synthesized La-MIL-101(Fe)-NH2@SiO2 yolk-shell nanocomposites with superior pH stability for efficient and selective phosphorus recovery - Shuangli Li; Yu Zhang; Sen Qiao; Jiti Zhou (Journal of Water Process Engineering, 2023)

Allergenicity of wheat protein in diet: Mechanisms, modifications and challenges - Ming Liu; Jihong Huang; Sen Ma; Guanghai Yu; Aimei Liao; Long Pan; Yinchen Hou (Food Research International, 2023)

An accurate and efficient method for simultaneous determination of 16 trichothecenes in maize and wheat by UHPLC-Q-Orbitrap-HRMS combined one-step pretreatment with a novel isotope multipoint calibration strategy - Yu Wu; Jin Ye; Songshan Wang; Xiaomin Han; Li Li; Lin Zhu; Sen Li; Hongmei Liu; Yang Wang; Yi Shao; Songxue Wang (Food Control, 2023)

An optimization neural network model for bridge cable force identification - Tongtong Gai; Dehu Yu; Sen Zeng; Jerry Chun-Wei Lin (Engineering Structures, 2023)

A multifunctionally reversible detector: Photoacoustic and dual-channel fluorescence sensing for SO2/H2O2 - Yicai Zhu; Junjun Wang; Yingyong Ni; Qingpeng Rao; Xiaojiao Zhu; Jianhua Yu; Sen Wang; Hongping Zhou (Analytica Chimica Acta, 2023)

Partial reuse of circadian clock genes along parallel clines of diapause in two moth species - Yue Yu; Li‐Li Huang; Fang‐Sen Xue; Erik B. Dopman (Molecular Ecology, 2023)
Understanding the molecular basis of repeated evolution improves our ability to predict evolution across the tree of life. Only since the last decade has high‐throughput sequencing enabled comparative genome scans to thoroughly examine the repeatability of genetic changes driving repeated phenotypic evolution. The Asian corn borer (ACB), Ostrinia furnacalis (Guenée), and the European corn borer (ECB), Ostrinia nubilalis (Hübner), are two closely related moths displaying repeatable phenological adaptation to a wide range of climates on two separate continents, largely manifesting as changes in the timing of diapause induction and termination across latitude. Candidate genes underlying diapause variation in North American ECB have been previously identified. Here, we sampled seven ACB populations across 23 degrees of latitude in China to elucidate the genetic basis of diapause variation and evolutionary mechanisms driving parallel clinal responses in the two species. Using pooled whole‐genome sequencing (Pool‐seq) data, population genomic analyses revealed hundreds of single nucleotide polymorphisms (SNP) whose allele frequencies covaried with mean diapause phenotypes along the cline. Genes involved in circadian rhythm were over‐represented among candidate genes with strong signatures of spatially varying selection. Only one of two circadian clock genes associated with diapause evolution in ECB showed evidence of reuse in ACB (period [ per ]), but per alleles were not shared between species nor with their outgroup, implicating independent mutational paths. Nonetheless, evidence of adaptive introgression was discovered at putative diapause loci located elsewhere in the genome, suggesting that de novo mutations and introgression might both underlie the repeated phenological evolution.

Preparation and properties of modified starch-based low viscosity and high consolidation foam dust suppressant - Rongxiao Xu; Haiming Yu; Hui Dong; Yuxi Ye; Sen Xie (Journal of Hazardous Materials, 2023)

Extending shelf life of chilled pork meat by cinnamaldehyde nano emulsion at non-contact mode - Fei Liu; Chunhua Yu; Shiliang Guo; Bor-Sen Chiou; Mengwei Jia; Feifei Xu; Maoshen Chen; Fang Zhong (Food Packaging and Shelf Life, 2023)

Sex-specific effects of propiconazole on the molting of the Chinese mitten crab (Eriocheir sinensis) - Chunlian Yao; Lina Yu; Lan Huang; Yajie Chen; Xuanjun Guo; Niannian Cao; Zhuoying Liu; Jie Shen; Xuefeng Li; Sen Pang; Changsheng Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

The sensitivity of mechanical properties and pore structures of Beishan granite to large variation of temperature in nuclear waste storage sites - Yun Wu; Li-Hua Hu; Jin Yu; Xiao-Zhao Li; Li-Ning Yang; Sen Xue; Kai Zhang (Environmental Science and Pollution Research, 2023)

Characteristics and provenances of rare earth elements and Nd isotopes in surface sediments of mangrove wetlands in the Jiulong River Estuary, China - Bo-sen Weng; Rui-an Wan; Rui-lian Yu; Gong-ren Hu; Yu Yan; Cheng-qi Lin; Hua-bin Huang (Environmental Science and Pollution Research, 2023)

Muyocoxanthones O–S: Undescribed xanthones with antioxidative damage bioactivity to cardiomyocytes from the endophytic fungus Muyocopron laterale - Hai-Yan Cao; Sen-feng Sun; Cheng Yi; Chen-yu Yang; Ke-liang Chen; Xiao-wei Zhang; Yun-Bao Liu (Phytochemistry, 2023)

Effects and mechanisms of extremely cold environment on body response after trauma - Yu-Yuan Peng; Xiu-Min Lu; Sen Li; Can Tang; Yang Ding; Hai-Yan Wang; Ce Yang; Yong-Tang Wang (Journal of Thermal Biology, 2023)

Morphologies, kinetics and structures of methane hydrate in the system containing tetrahydrofuran and cyclopentane - Hao-Yang Li; Xiao-Sen Li; Yi-Song Yu; Zhao-Yang Chen (Fuel, 2023)

Collagen films with improved wet state mechanical properties by mineralization - Fei Liu; Kaidi Zhu; Yuxin Ma; Zhe Yu; Bor-Sen Chiou; Mengwei Jia; Maoshen Chen; Fang Zhong (Food Hydrocolloids, 2023)

A new strategy to alleviate the obesity induced by endocrine disruptors—A unique lysine metabolic pathway of nanoselenium Siraitia grosvenorii to repair gut microbiota and resist obesity - Yu Wang; Wei Sun; Sen Yan; Zhiyuan Meng; Ming Jia; Sinuo Tian; Shiran Huang; Xiaoxuan Sun; Shihang Han; Canping Pan; Jinling Diao; Qiuxia Wang; et al. (Food and Chemical Toxicology, 2023)

A one-step regeneration method in-situ for deactivated aluminum-based lithium adsorbent used in high Mg2+/Li+ brines - Jun Chen; Jianglong Du; Jianguo Yu; Sen Lin (Desalination, 2023)

Identification of genetic loci associated with five agronomic traits in alfalfa using multi-environment trials - Sen Lin; Cesar A. Medina; Guojie Wang; David Combs; Glenn Shewmaker; Steve Fransen; Don Llewellyn; Steven Norberg; Long-Xi Yu (Theoretical and Applied Genetics, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Two new chemical constituents from the leaves of Illicium dunnianum - Jun-Ran Shao; Sen-Ju Ma; Ting Li; Xiao-Qing He; Zhen-Zhong Wang; Wei Xiao; Xin-Sheng Yao; Hai-Bo Li; Yang Yu (Natural Product Research, 2023)

Influence law of structural parameters of pressure-swirl nozzle on atomization effect based on multiscale model - Yao Xie; Yuxi Ye; Haiming Yu; Weimin Cheng; Sen Xie; Junwei Zhao (Environmental Science and Pollution Research, 2023)

Transition of carbon-nitrogen coupling under different anthropogenic disturbances in subtropical small mountainous rivers - Li-Chin Lee; Gabriele Weigelhofer; Thomas Hein; Shin-Chien Chan; Ying-San Liou; Chien-Sen Liao; Fuh-Kwo Shiah; Yu-Lin Yu; Tsung-Yu Lee; Jr-Chuan Huang (Science of The Total Environment, 2023)

Study on the coal dust deposition fraction and site in the upper respiratory tract under different particle sizes and labor intensities - Yu Cheng; Haiming Yu; Sen Xie; Junwei Zhao; Yuxi Ye (Science of The Total Environment, 2023)

Eliminating temporal correlation in quantum-dot entangled photon source by quantum interference - Run-Ze Liu; Yu-Kun Qiao; Han-Sen Zhong; Zhen-Xuan Ge; Hui Wang; Tung-Hsun Chung; Chao-Yang Lu; Yong-Heng Huo; Jian-Wei Pan (Science Bulletin, 2023)

Nano-sized alumina supported palladium catalysts for methane combustion with excellent thermal stability - Wei Shi; Guangyan Xu; Xuewang Han; Yingjie Wang; Zhi Liu; Sen Xue; Nannan Sun; Xiaoyan Shi; Yunbo Yu; Hong He (Journal of Environmental Sciences, 2023)

Melon yellow-green plant (Cmygp) encodes a Golden2-like transcription factor regulating chlorophyll synthesis and chloroplast development - Sen Yang; Xiaojuan Wang; Wenkai Yan; Yu Zhang; Pengyao Song; Yaomiao Guo; Kuixi Xie; Jianbin Hu; Juan Hou; Yufeng Wu; Huayu Zhu; Shouru Sun; et al. (Theoretical and Applied Genetics, 2023)

Quantitative trait loci mapping for heading date and spikelet number in wheat (Triticum aestivum L.)based on two recombinant inbred line populations - Wenjing Hu; Dongmei Zhu; Yu Zhang; Jiang Liu; Die Zhao; Sen Liao; Jizeng Jia; Weigang Xu (Genetic Resources and Crop Evolution, 2023)

Damage evolution and acoustic emission characteristics of hydrochemically corroded limestone - Yang Yu; Jun Wang; Guang-Liang Feng; Da-Xin Geng; Hao-Sen Guo (Bulletin of Engineering Geology and the Environment, 2023)

Osmoregulation, physiological metabolism, and oxidative stress responses to water salinity in adult males of Chinese mitten crabs (Eriocheir sinensis) - Xin Wang; Zhi-xin Guo; Xin-yu Lei; Sen Wang; Ji-wu Wan; Hong-jian Liu; Yu-ke Chen; Yun-long Zhao; Gui-qin Wang; Qiu-ju Wang; Dong-ming Zhang (Aquaculture International, 2023)

Bufalin reverses cancer-associated fibroblast-mediated colorectal cancer metastasis by inhibiting the STAT3 signaling pathway - Haijing Wang; Jinbao Chen; Sen Li; Jiahua Yang; Donghao Tang; Wentao Wu; Kun Yu; Yijun Cao; Ke Xu; Peihao Yin; Yi Chen; Wei Li (Apoptosis, 2023)

Study on the effect law of virtual impact separator efficiency based on multi-factor orthogonal test - Yuhuan Wang; Haiming Yu; Xianhang Yang; Sen Xie; Yuxi Ye; Chuangen Hou; Tianyuan Gao (Process Safety and Environmental Protection, 2023)

Halogen microregulation in metal-organic frameworks for enhanced adsorption performance of ReO4-/TcO4- - Qing-Hua Hu; You-Gan Wang; Xin Gao; Yu-Zhen Shi; Sen Lin; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Influence of modified biochar supported sulfidation of nano-zero-valent-iron (S-nZVI/BC) on nitrate removal and greenhouse gas emission in constructed wetland - Fanlong Kong; Junru Wang; Weihao Hou; Yuqian Cui; Lihua Yu; Yi Zhang; Sen Wang (Journal of Environmental Sciences, 2023)

Sulfide-driven nitrous oxide recovery during the mixotrophic denitrification process - Cong Yu; Sen Qiao; Jiti Zhou (Journal of Environmental Sciences, 2023)

A predictive model on deoxynivalenol in harvested wheat in China: Revealing the impact of the environment and agronomic practicing - Sen Li; Ningjing Liu; Di Cai; Cheng Liu; Jin Ye; Bingjie Li; Yu Wu; Li Li; Songxue Wang; H.J. van der Fels-Klerx (Food Chemistry, 2023)

The effect of volatile compounds of Syzygium aromaticum flower buds against Aspergillus flavus growth on wheat grain at postharvest stage - Yu-Liang Qin; Shuai-Bing Zhang; Wen-Zheng Ding; Yang-Yong Lv; Huan-Chen Zhai; Shan Wei; Ping-An Ma; Yuan-Sen Hu (Food Control, 2023)

The sensitive mobility of Cr in ashes studied by SiO2–Al2O3–Fe2O3–CaO system - Zhe Yang; Yu Ning; Changxiang Wang; Sen Yang; Wei Zhang; Rainer Dähn; Yilian Li (Environmental Pollution, 2023)

High-Fat Diet Exacerbates Autistic-Like Restricted Repetitive Behaviors and Social Abnormalities in CC2D1A Conditional Knockout Mice - Yu-Chiao Wang; Chin-Hao Chen; Cheng-Yi Yang; Pin Ling; Kuei-Sen Hsu (Molecular Neurobiology, 2023)

Aerobic glycolysis in colon cancer is repressed by naringin via the HIF1A pathway - Guangtao Pan; Ping Zhang; Aiying Chen; Yu Deng; Zhen Zhang; Han Lu; Aoxun Zhu; Cong Zhou; Yanran Wu; Sen Li (Journal of Zhejiang University-SCIENCE B, 2023)

The Regularized WSM6 Microphysical Scheme and Its Validation in WRF 4D-Var - Sen Yang; Deqin Li; Liqiang Chen; Zhiquan Liu; Xiang-Yu Huang; Xiao Pan (Advances in Atmospheric Sciences, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Key factors controlling the kinetics of secondary hydrate formation in the porous media - Chang-Wen Xiao; Xiao-Sen Li; Gang Li; Yang Yu; Yi-Fan Weng; Qiu-Nan Lv; Jian-Xing Yu (Gas Science and Engineering, 2023)

The Adsorption and Desorption Behavior of Bisphenol A on Five Microplastics Under Simulated Gastrointestinal Conditions - Hui Jiang; Qiao-ying Li; Jiao-xia Sun; Yu-feng Mao; Xin Liu; Sisi Que; Weiwei Yu; Yi-sen Kan (Water, Air, & Soil Pollution, 2023)

Moderate-Intensity Treadmill Exercise Promotes mTOR-Dependent Motor Cortical Neurotrophic Factor Expression and Functional Recovery in a Murine Model of Crush Spinal Cord Injury (SCI) - Zuxiong Zhan; Lu Pan; Ying Zhu; Yunhang Wang; Qin Zhao; Yuan Liu; Sen Li; Haiyan Wang; Ce Yang; Lehua Yu; Ying Yin; Botao Tan (Molecular Neurobiology, 2023)

A novel strategy for arsenic removal from acid wastewater via strong reduction processing - Zhi Feng; Yu Ning; Sen Yang; Jinhao Yu; Weiwei Ouyang; Yilian Li (Environmental Science and Pollution Research, 2023)

The tiered transaction system for sea use rights in China: Theoretical basis and market construction - Xuan Yu; Sen Lin; Weiteng Shen; Qi Chen (Marine Policy, 2023)

City-scale distribution of airborne antibiotic resistance genes - Xin-Yuan Zhou; Hu Li; Shu-Yi-Dan Zhou; Yu-Sen Zhang; Jian-Qiang Su (Science of The Total Environment, 2023)

A new method of hotspot analysis on the management of CO2 and air pollutants, a case study in Guangzhou city, China - Li Zhang; Muchuan Niu; Zhe Zhang; Jizhang Huang; Lingyun Pang; Pengcheng Wu; Cheng Lv; Sen Liang; Mengbing Du; Mingyu Li; Libin Cao; Yu Lei; et al. (Science of The Total Environment, 2023)

Thermodynamic characteristics of methane hydrate formation in high-pressure microcalorimeter under different reaction kinetics - Juan Fu; Jia-Mei Mo; Shi-Jun Liu; Wen-Zhe Yi; Yi-Song Yu; Neng-You Wu; Xiao-Li Chen; Qiu-Cheng Su; Xiao-Sen Li (Fuel, 2023)

Nontargeted metabolomic analysis of four different parts of Actinidia arguta by UPLC-Q-TOF-MSE - Yu-fei Hou; Lu Bai; Sen Guo; Jia-bing Hu; Shan-shan Zhang; Shao-jing Liu; Ying Zhang; Shiming Li; Chi-Tang Ho; Nai-sheng Bai (Food Research International, 2023)

Enhancement of uniformity and performance of LiFePO4/C cathode material prepared via a continuous rotating reactor - Ting Zhang; Sen Lin; Jianguo Yu (Chemical Engineering Journal, 2023)

Phytochemical and underlying mechanism of Mikania micrantha Kunth on antibiotic resistance genes, and pathogenic microbes during chicken manure composting - Yousif Abdelrahman Yousif Abdellah; Yu-Sen Luo; Shan-Shan Sun; Xi Yang; Hong-Yi Ji; Rui-Long Wang (Bioresource Technology, 2023)

Review and prospects of mining chemical dust suppressant: classification and mechanisms - Hui Dong; Haiming Yu; Rongxiao Xu; Weimin Cheng; Yuxi Ye; Sen Xie; Junwei Zhao; Yu Cheng (Environmental Science and Pollution Research, 2023)

Design and Optimization of Multipoint Sampler for Seafloor Sediment Carried by a Deep-Sea Landing Vehicle - Yan Gao; Yue Zhou; Wei Guo; Yifan Fu; Sen Gao; Zhenzhuo Wei; Hongming Sun; Yu Sun (Journal of Marine Science and Engineering, 2022)
The present study proposes a low-energy consumption multipoint sampler carried by a deep-sea landing vehicle (DSLV) to meet the requirements of time series sampling in local areas and location series sampling in wide areas, and an optimization method of sampling structure based on least-squares support-vector machine (LSSVM) surrogate model and a multi-objective particle swarm optimization (MOPSO) algorithm. First, the overall structure and core components, such as the multipoint sampler’s sampling structure, were designed. The optimization variables were the cone angle, sampling tube inner diameter, and sampling tube inner hole length, which were determined by considering the force with which the sampling structure penetrates the seafloor sediment. Then, the sampling process was simulated by the finite element method-smoothed particle hydrodynamics (FEM-SPH) method, while the accurate LSSVM model of force required for sampling and sampling tube volume was established. Finally, the MOPSO algorithm was used for multi-objective optimization of model parameters of sampling structure. The optimal model of sampling structure that can provide theoretical support for the optimal design of multipoint sampler effectively reduces energy consumption and improves sampling efficiency by force required for sampling 25.89% lower and sampling tube volume 34.81% higher than the original model.

Geraniin as a potential inhibitor of SARS-CoV-2 3CL pro - Wen-Di Yu; Qi-Ying Jin; Mao-Sen Zeng; Jin-Yuan Liu; Pei-Ping Xu (Natural Product Research, 2022)

Effects of montmorillonite on the adsorption of Fe(II) by ferrihydrite and its phase transformation at different pH - Chang He; Zhe Yang; Yu Ning; Sen Yang; Fengcheng Jiang; Jiayi Zhang (Environmental Science and Pollution Research, 2022)

Regulation intensity, environmental disclosure, and cost of capital: evidence from listed firms in China - Sen Yan; Wenpeng Na; Xueying Yu; Xuhang Zhang (Environmental Science and Pollution Research, 2022)

Reduced Utilization Process Leaching Toxicity by Stabilizing Heavy Metals in Fly Ash from MSW Incineration Based on Hydrothermal Oxidation - Xueru Yu; Kai Zhou; Tong Zhang; Bo Bian; Sen Chen (Bulletin of Environmental Contamination and Toxicology, 2022)

Deciphering the Heterogeneity of Mitochondrial Functions During Hematopoietic Lineage Differentiation - Haoyue Liang; Shuxu Dong; Weichao Fu; Sen Zhang; Wenying Yu; Fang Dong; Baolin He; Jinhong Wang; Yingdai Gao; Yuan Zhou; Yongxin Ru (Stem Cell Reviews and Reports, 2022)

Nature-based solutions for securing contributions of water, food, and energy in an urban environment - Mei-Hua Yuan; Fang-Chen Lo; Chang-Ping Yu; Hsin-hsin Tung; Yu-Sen Chang; Pei-Te Chiueh; Hsin-Chieh; Huang; Chao-Chin Chang; Chung-Yu Guan; Chun-Wei Wu; Zi-Xuan Xu; et al. (Environmental Science and Pollution Research, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

IDDLncLoc: Subcellular Localization of LncRNAs Based on a Framework for Imbalanced Data Distributions - Yan Wang; Xiaopeng Zhu; Lili Yang; Xuemei Hu; Kai He; Cuinan Yu; Shaoqing Jiao; Jiali Chen; Rui Guo; Sen Yang (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Shear Instability and Turbulent Mixing in the Stratified Shear Flow Behind a Topographic Ridge at High Reynolds Number - Jia-Lin Chen; Xiao Yu; Ming-Huei Chang; Sen Jan; Yiing Jang Yang; Ren-Chieh Lien (Frontiers in Marine Science, 2022)
Observations on the lee of a topographic ridge show that the turbulence kinetic energy (TKE) dissipation rate due to shear instabilities is three orders of magnitude higher than the typical value in the open ocean. Laboratory-scale studies at low Reynolds number suggest that high turbulent dissipation occurs primarily within the core region of shear instabilities. However, field-scale studies indicate that high turbulence is mainly populated along the braids of shear instabilities. In this study, a high-resolution, resolving the Ozmidov-scale, non-hydrostatic model with Large Eddy Simulation (LES) turbulent closure is applied to investigate dominant mechanisms that control the spatial and temporal scales of shear instabilities and resulting mixing in stratified shear flow at high Reynolds number. The simulated density variance dissipation rate is elevated in the cusp-like bands of shear instabilities with a specific period, consistent with the acoustic backscatter taken by shipboard echo sounder. The vertical length scale of each cusp-like band is nearly half of the vertical length scale of the internal lee wave. However, it is consistent with instabilities originating from a shear layer based on linear stability theory. The model results indicate that the length scale and/or the period of shear instabilities are the key parameters to the mixing enhancement that increases with lateral Froude number Fr L , i.e. stronger shear and/or steeper ridge.

Black-Box Modelling and Prediction of Deep-Sea Landing Vehicles Based on Optimised Support Vector Regression - Hongming Sun; Wei Guo; Yanjun Lan; Zhenzhuo Wei; Sen Gao; Yu Sun; Yifan Fu (Journal of Marine Science and Engineering, 2022)
Due to the nonlinearity of the deep-seafloor and complexity of the hydrodynamic force of novel structure platforms, realising an accurate motion mechanism modelling of a deep-sea landing vehicle (DSLV) is difficult. The support vector regression (SVR) model optimised through particle swarm optimisation (PSO) was used to complete the black-box motion modelling and vehicle prediction. In this study, first, the prototype and system composition of the DSLV were proposed, and subsequently, the high-dimensional nonlinear mapping relationship between the motion state and the driving forces was constructed using the SVR of radial basis function. The high-precision model parameter combination was obtained using PSO, and, subsequently, the black-box modelling and prediction of the vehicle were realised. Finally, the effectiveness of the method was verified through multi-body dynamics simulation and scaled test prototype data. The experimental results confirmed that the proposed PSO–SVR model could establish an accurate motion model of the vehicle, and provided a high-precision motion state prediction. Furthermore, with less calculation, the proposed method can reliably apply the model prediction results to the intelligent behaviour control and planning of the vehicle, accelerate the development progress of the prototype, and minimise the economic cost of the research and development process.

Ocean Currents May Influence the Endolithic Bacterial Composition in Coral Skeletons - Po-Yu Liu; Sung-Yin Yang; Chih-Ying Lu; Naohisa Wada; Stéphane De Palmas; Shu-Shuo Yeh; Hideyuki Yamashiro; Sen-Lin Tang; Shan-Hua Yang (Frontiers in Marine Science, 2022)
Coral endolithic microbes can be an important nutrients support for hosts while under stresses. Previous studies have found that the endolithic microbial composition of a single coral species can be biogeographical diverse. However, the potential environmental factors, such as salinity, temperature, pH, and nutrient, that might influence the composition of the endolithic microbes remain unclear. In this study, we used both amplicon sequence variants (ASV) and a kmer-based taxonomic unit (KTU) to characterize the endolithic bacterial constitution of Isopora spp. located in the western Pacific Ocean—where it is subjected to the Kuroshio Current (in Okinawa, Japan and Green Island, Taiwan)—and the South China Sea (Dongsha Atoll). The endolithic bacterial community compositions showed a significant geographical difference, and we suggest that the ocean current and primary productivity are the most essential environmental factors influencing the bacterial communities in the skeleton of Isopora spp. In addition, our results showed that, technically, compared to ASV, bacterial composition based on KTU avoids extreme data, making it a suitable tool for explaining the associations between microbes and environmental factors.

Two new chemical constituents from the rhizomes of Actaea dahurica - Sen-Ju Ma; Hai-Bo Li; Jun-Ran Shao; Qian-Qian Pang; Ting Li; Xin-Sheng Yao; Yang Yu (Natural Product Research, 2022)

Zooplankton Community Structure in Changli Near Shore Area of Hebei Province, China - Yang Yu; Sen Yang; Xinggui Zhao; Zhanguang Liu; Xianbin Liu (Thalassas: An International Journal of Marine Sciences, 2022)

Three new Coltricia (Hymenochaetaceae, Basidiomycota) species from China based on morphological characters and molecular evidence - Lu-Sen Bian; Meng Zhou; Jian Yu (Mycological Progress, 2022)

Electrochemical enhancement of high-efficiency wet removal of mercury from flue gas - Nai-jiao Xu; Sen Li; Yu-hong Fu; Zhao-yang Wang; Li-juan Feng; Ji Wang (Environmental Science and Pollution Research, 2022)

Effects of different stocking densities on the growth performance and antioxidant capacity of Chinese mitten crab (Eriocheir sinensis) in rice crab culture system - Xin Wang; Qi Yao; Xin-yu Lei; Dong-ming Zhang; Sen Wang; Ji-wu Wan; Hong-jian Liu; Yu-ke Chen; Yun-long Zhao; Gui-qin Wang; Qiu-ju Wang; Zhi-xin Guo (Aquaculture International, 2022)

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

A First Insight Into the Heat-Induced Changes in Proteomic Profiles of the Coral Symbiotic Bacterium Endozoicomonas montiporae - Ya-Fan Chan; Chia-Yu Chen; Chih-Ying Lu; Yung-Chi Tu; Kshitij Tandon; Shinya Shikina; Sen-Lin Tang (Frontiers in Marine Science, 2022)
Endozoicomonas , a core bacterial group in corals, may also be a coral symbiont. Endozoicomonas communities often decrease rapidly in corals under heat stress. However, how the bacteria respond to changes in temperature and coral host during heat stress is unknown. Here, we employed the cultivable, dominant species E. montiporae as a working organism to explore how Endozoicomonas responds to heat stress. We designed two experiments to clarify the extent to which E. montiporae is influenced by temperature and coral host. We detected differentially expressed protein (DEP) profiles in this bacterium at 31 and 33°C compared to 25°C by tandem mass tags-based quantitative proteome analysis. Fifty DEPs, including many heat shock proteins, were detected when the temperature changed. The expression of antioxidant defense proteins and key pyruvate synthase proteins decreased, suggesting that E. montiporae were in a physiology of stress at 33°C. Furthermore, some proteins were differentially expressed because of the heat-stress-treated coral lysate specifically, suggesting that not only heat but also heat-induced host factors can affect the protein expression of the bacterium. This study provides an in-depth analysis of how the molecular mechanisms of Endozoicomonas are affected by heat stress and coral host.

Short-term lime application impacts microbial community composition and potential function in an acid black soil - Sen Li; Junjie Liu; Qin Yao; Zhenhua Yu; Yansheng Li; Jian Jin; Xiaobing Liu; Guanghua Wang (Plant and Soil, 2022)

Effects of organic acids on the chemotaxis profiles and biocontrol traits of antagonistic bacterial endophytes against root-rot disease in Panax notoginseng - Li Ma; Wu-Qin Wang; Rui Shi; Xue-Mei Zhang; Xin Li; Yu-Sen Yang; Ming He Mo (Antonie van Leeuwenhoek, 2021)

Geographic and subsequent biotic isolations led to a diversity anomaly of section Heterotropa (genus Asarum : Aristolochiaceae) in insular versus continental regions of the Sino‐Japanese Floristic Region - Daiki Takahashi; Shota Sakaguchi; Yu Feng; Yuji Isagi; Ying‐Xiong Qiu; Pan Li; Rui‐Sen Lu; Chang‐Tse Lu; Shih‐Wen Chung; Yang‐Shan Lin; Yun‐Chao Chen; Atsushi J. Nagano; et al. (Journal of Biogeography, 2021)
Aim The Sino‐Japanese Floristic Region has extremely high species diversity with respect to temperate plants; however, the reasons for this diversity are poorly understood because most studies have only considered geographic isolation caused by climatic oscillations. In some plant groups, high floral trait diversity and uneven species diversity between insular systems and the continental area suggest other factors may have important roles too. The primary purpose of this study is to reveal how abiotic and biotic factors have shaped the species diversity anomaly of Heterotropa between the insular systems and the continental area. Location The Sino‐Japanese Floristic Region. Taxon Section Heterotropa (genus Asarum ; Aristolochiaceae). Methods Using ddRAD‐seq and chloroplast genome data, we built a time‐calibrated phylogenetic tree including 79 species. We estimated the patterns of floral traits (flowering time and floral size) evolution using macroevolutionary modelling, and tested the correlation of speciation rate with the trait evolution rates. Finally, we estimated the isolation factors of all taxa pairs and sister‐taxa pairs based on distribution range and floral traits. Results Phylogenetic analysis indicated that Heterotropa was diverged into two clades (continental clade and insular clade) in the Miocene, and the major subclades corresponded to geographic entities. Most rate shifts accelerating floral trait's evolution occurred during the Pleistocene period. Evolution rate of floral traits showed positive correlation with the speciation rate. Large proportion of taxa in the insular clade are distributed allopatrically. Several sister pairs showed floral trait divergence with geographic overlap. Main Conclusions The diversification of Heterotropa appears to have been triggered by geographic and climatic events, and subsequent repeated floral trait evolution with and without geographic isolation. Furthermore, the high species diversity in the insular systems would have been formed by the repeated range fragmentations and contractions. Our study demonstrates the importance of multidimensional studies to understand the diversification process of temperate plants in the Sino‐Japanese Floristic Region.

Divergent Projection Patterns Revealed by Reconstruction of Individual Neurons in Orbitofrontal Cortex - Junjun Wang; Pei Sun; Xiaohua Lv; Sen Jin; Anan Li; Jianxia Kuang; Ning Li; Yadong Gang; Rui Guo; Shaoqun Zeng; Fuqiang Xu; Yu-Hui Zhang (Neuroscience Bulletin, 2021)

Pramipexole attenuates 6-OHDA-induced Parkinson’s disease by mediating the Nurr1/NF-κB pathway - Hua Gao; Dan Wang; Yu-Ling Wang; Jie-Ping Mao; Sen Jiang; Xin-Ling Yang (Molecular Biology Reports, 2021)

Effects of plant growth regulators and polyamines on bract longevity in Bougainvillea buttiana - Kuan-Hung Lin; Jui-Mei Li; Chun-Wei Wu; Yu-Sen Chang (Horticulture, Environment, and Biotechnology, 2021)

Shallow gas hydrates off southwest Taiwan and their mechanisms - Yin-Sheng Huang; Shu-Kun Hsu; Chih-Chieh Su; Andrew Tien-Shun Lin; Pai-Sen Yu; Nathalie Babonneau; Gueorgui Ratzov; Serge Lallemand; Pi-Chuen Huang; Shiao-Shan Lin; Jing-Yi Lin; Kuo-Yen Wei; et al. (Marine Geophysical Research, 2021)
We have collected two shallow gas hydrate samples at two sites having different geological settings off southwest Taiwan during the cruise MD214 in 2018. The first core site, MD18-3542, is on the South Yuan-An East Ridge at ~ 1200 m water deep, where a structural unconformity covered by fine-silt sediments appears at ~ 5.5 m below the seafloor. The second core site, MD18-3543, is close to the Good-Weather Ridge at ~ 1100 m water deep, where a gas-related pockmark structure and authigenic carbonates are present at shallow strata with fine-silt sediments near the seafloor. Sediment properties of core MD18-3542 are distinctively different above and below the layer corresponding to the unconformity. Both cores show obvious gaps or voids in the lower core halves. The core features could be linked to the dissociated methane upward migrating from deep strata. Core site settings with upwelling methane would favor the formation of shallow gas hydrates. At site MD18-3542, the shallow hydrate could be formed due to high concentration methane kept beneath the unconformity covered by fine-silt sediments. At site MD18-3543, the shallow hydrate could be formed due to an extremely high flux of upwelling methane trapped either beneath the authigenic carbonates or fine-silt sediments.

Characterization and analysis of the transcriptome response to drought in Larix kaempferi using PacBio full-length cDNA sequencing integrated with de novo RNA-seq reads - Wenlong Li; Joobin Lee; Sen Yu; Fude Wang; Wanqiu Lv; Xin Zhang; Chenghao Li; Jingli Yang (Planta, 2021)

Relationship Between Body Composition and Balance Performance in Older Adults with Hyperkyphosis - Phunsuk Kantha; Shiow-Chwen Tsai; Chien-Wen Hou; Rong-Sen Yang; Pei-Yu Su; Wei-Li Hsu (Journal of Medical and Biological Engineering, 2021)

Archaeobotanical evidence reveals the human–environment interactions during the 9th–13th centuries at Turpan, Xinjiang on the ancient Silk Road - Yi-Feng Yao; Xia Wang; Wu Guo; Hong-En Jiang; Min Li; David K. Ferguson; Yu-Fei Wang; Cheng-Sen Li (Vegetation History and Archaeobotany, 2020)

Molecular phylogeny and morphology reveal two new species of Coltricia (Hymenochaetaceae Basidiomycota) from China - Lu-Sen Bian; Yu-Cheng Dai (Mycological Progress, 2020)

Effects of supplying silicon nutrient on utilization rate of nitrogen and phosphorus nutrients by rice and its soil ecological mechanism in a hybrid rice double-cropping system - Min Liao; Zhi-ping Fang; Yu-qi Liang; Xiao-hui Huang; Xu Yang; Shu-sen Chen; Xiao-mei Xie; Chang-xu Xu; Jia-wen Guo (Journal of Zhejiang University-SCIENCE B, 2020)

Erratum to: Exosome-derived galectin-9 may be a novel predictor of rejection and prognosis after liver transplantation - Ai-bin Zhang; Yi-fan Peng; Jun-jun Jia; Yu Nie; Shi-yu Zhang; Hai-yang Xie; Lin Zhou; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2020)

Genome Shuffling of Bacillus velezensis for Enhanced Surfactin Production and Variation Analysis - Liang Chen; Xing-yu Chong; Ying-Ying Zhang; Yang-yong Lv; Yuan-Sen Hu (Current Microbiology, 2020)

Correction to: Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

DESIGN AND TYPE SELECTION OF CONCRETE‐LINED SMALL CANALS IN CUT AND EXPANSIVE SOIL IN COLD REGIONS - Sen‐Hao Cheng; Liang Wang; Yu‐Bao Wang; Zheng‐Zhong Wang; Bernard A. Engel (Irrigation and Drainage, 2019)
In cold regions, deformation because of frost heave in the soil seriously damages the concrete lining of canals, which results in seepage loss and high maintenance costs. Cross‐sectional canal shapes with low‐stress concrete lining are an important aspect of small canal design. Round‐bottom triangular, parabolic and catenary sections are curved and therefore regarded as likely to perform well in conditions in which frost heave occurs. This study provides an objective answer to the question of which section would perform well in frost heave conditions with as large as possible water conveyance efficiency. The design process of small canals was simplified first, and the result shows savings in the land area required for canals. Then, based on two principles, the hydraulic radius and performance of three sections in resisting frost heave damage were compared. In regions without frost heave, the round‐bottom triangular section is better because it has the largest hydraulic radius and design flexibility. In cold regions, if width to depth ratio or depth is a principal constraint, a parabolic (wide section) or catenary (narrow section) is better for big side slopes and curved structures. If side slope (horizontal to vertical) is the principal constraint, the round‐bottom triangular is better. © 2019 John Wiley & Sons, Ltd.

A Non-innocent Magnesium Organoclay-Based Drug Vehicle for Improving the Cancer Therapy Effect of Methotrexate - Jinyu Li; Sen Qiao; Guoxin Tan; Yibin Yu; Dandan Liu; Weisan Pan (AAPS PharmSciTech, 2019)

Perineuronal Nets Restrict the Induction of Long-Term Depression in the Mouse Hippocampal CA1 Region - Guan Hock Khoo; Yu-Ting Lin; Tsung-Chih Tsai; Kuei-Sen Hsu (Molecular Neurobiology, 2019)

Correction to: Effects of AMPK on Apoptosis and Energy Metabolism of Gastric Smooth Muscle Cells in Rats with Diabetic Gastroparesis - Mo-han Zhang; Xue-sen Fang; Jun-yu Guo; Zheng Jin (Cell Biochemistry and Biophysics, 2019)

Exosome-derived galectin-9 may be a novel predictor of rejection and prognosis after liver transplantation - Ai-bin Zhang; Yi-fan Peng; Jun-jun Jia; Yu Nie; Shi-yu Zhang; Hai-yang Xie; Lin Zhou; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2019)

Effects of AMPK on Apoptosis and Energy Metabolism of Gastric Smooth Muscle Cells in Rats with Diabetic Gastroparesis - Mo-han Zhang; Xue-sen Fang; Jun-yu Guo; Zheng Jin (Cell Biochemistry and Biophysics, 2019)

Lasiodiplodia spp. associated with Aquilaria crassna in Laos - Yu Wang; Sen Lin; Lin Zhao; Xiang Sun; Wei He; Ying Zhang; Yu-Cheng Dai (Mycological Progress, 2019)

Magma–magma interaction in the mantle recorded by megacrysts from Cenozoic basalts in eastern China - Xun Yu; Gang Zeng; Li-Hui Chen; Sen-Lin Hu; Zhi-Qiang Yu (International Geology Review, 2019)

An H-ferritin from the hydrothermal vent shrimp Rimicaris exoculata and its potential role in iron metabolism - Xiao-Li Liu; Sen Ye; Hua-Wei Li; Bo Lu; Yan-Qin Yu; Yu-Peng Fan; Wei-Jun Yang; Jin-Shu Yang (BioMetals, 2019)

Relative soil moisture in China’s farmland - Guofeng Zhu; Hanxiong Pan; Yu Zhang; Huiwen Guo; Leilei Yong; Qiaozhuo Wan; Huiying Ma; Sen Li (Journal of Geographical Sciences, 2019)

Polymorphism of duck MHC class molecules - Lin Zhang; Dongmei Lin; Sen Yu; Junping Bai; Wanchun Jiang; Wenzheng Su; Yanyan Huang; Shaohua Yang; Jiaqiang Wu (Immunogenetics, 2019)

Effects of insulin-like growth factor-1 on endoplasmic reticulum stress and autophagy in rat gastric smooth muscle cells cultured at different glucose concentrations in vitro - Xue-sen Fang; Mo-han Zhang; Jun-yu Guo; Zheng Jin (Molecular and Cellular Biochemistry, 2019)

Pollutant source analysis and tempo-spatial analysis of pollutant discharge intensity in a transboundary river basin - Hongwei Lu; Sen Yu (Environmental Science and Pollution Research, 2019)

Aristololactam derivatives from the fruits of Aristolochia contorta Bunge - Hao-Wei Ma; Cun-Zhu Dong; Xue-Ming Zhou; Miao-Miao Bu; Sen-Quan Yu (Natural Product Research, 2018)

Using a wheat-rye amphihaploid population to map a rye gene responsible for dwarfness - Sen Yang; Hongjing Zhu; Jianjun Yu; YuYang Zhong; LaiBin Zhao; YunFeng Jiang; Ming Hao; Lianquan Zhang; Shunzong Ning; XueJiao Chen; Dengcai Liu; Zhongwei Yuan (Euphytica, 2018)

Late Mesozoic Tectonic Evolution of Southwestern Fujian Province, South China: Constraints from Magnetic Fabric, Zircon U-Pb Geochronology and Structural Deformation - Sen Wang; Da Zhang; Ganguo Wu; Xingjian Li; Xiaoqiao Gao; Absai Vatuva; Yuan Yuan; Tengda Yu; Yu Bai; Ye Fang (Journal of Earth Science, 2018)

Using major nutrient concentrations to derive vertical movement of water masses in the coastal region of eastern Taiwan - Su-Cheng Pai; Sen Jan; Tung-Yuan Ho; Jin-Yuan Liu; Ken-Sheng Chu; Wen-Huei Lee; Cheng-Yun Wang; Ping-Yi Huang; Hung-Yu Hsu; Yiing-Jang Yang (Journal of Oceanography, 2017)

Neonatal Dexamethasone Treatment Exacerbates Hypoxia/Ischemia-Induced White Matter Injury - Chia -Yu Yeh; Che-Ming Yeh; Ting-Hsuan Yu; Kan-Hsun Chang; Chiung-Chun Huang; Kuei-Sen Hsu (Molecular Neurobiology, 2017)

An overlooked nitrogen loss linked to anaerobic ammonium oxidation in estuarine sediments in China - Xiao-Ru Yang; Bo-Sen Weng; Hu Li; Christopher W. Marshall; Hong Li; Yong-Shan Chen; Shen Yu; Gui-Bing Zhu; Yong-Guan Zhu (Journal of Soils and Sediments, 2017)

Tbx18-dependent differentiation of brown adipose tissue-derived stem cells toward cardiac pacemaker cells - Lei Chen; Zi-Jun Deng; Jian-Sheng Zhou; Rui-Juan Ji; Xi Zhang; Chuan-Sen Zhang; Yu-Quan Li; Xiang-Qun Yang (Molecular and Cellular Biochemistry, 2017)

Identification of Novel Compound Mutations in PLA2G6-Associated Neurodegeneration Patient with Characteristic MRI Imaging - Sen Guo; Liu Yang; Huijie Liu; Wei Chen; Jinchen Li; Ping Yu; Zhong Sheng Sun; Xiang Chen; Jie Du; Tao Cai (Molecular Neurobiology, 2017)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

A Brillouin scattering study of hydrous basaltic glasses: the effect of H2O on their elastic behavior and implications for the densities of basaltic melts - Lei Wu; De-Bin Yang; Jun-Xiu Liu; Bo Hu; Hong-Sen Xie; Fang-Fei Li; Yang Yu; Wen-Liang Xu; Chun-Xiao Gao (Physics and Chemistry of Minerals, 2017)

Song frequency correlates with latitude and individual body size in the cicada Mogannia formosana Matsumura (Hemiptera: Cicadidae) - Bao-Sen Shieh; Shih-Hsiung Liang; Chen-Yu Liao; Yuh-Wen Chiu (acta ethologica, 2017)

IP-10/CXCR3 Axis Promotes the Proliferation of Vascular Smooth Muscle Cells through ERK1/2/CREB Signaling Pathway - Hui-jin Wang; Yu Zhou; Rui-ming Liu; Yuan-sen Qin; Ying-huan Cen; Ling-yu Hu; Shen-ming Wang; Zuo-jun Hu (Cell Biochemistry and Biophysics, 2017)

Integrated prediction model for optimizing distributions of total amount of water pollutant discharge in the Songhua River watershed - Sen Yu; Hong-qiang Jiang; Miao Chang (Stochastic Environmental Research and Risk Assessment, 2016)

Interdecadal change in the lagged relationship between the Pacific–South American pattern and ENSO - Ruiqiang Ding; Jianping Li; Yu-heng Tseng; Kyung-Ja Ha; Sen Zhao; June-Yi Lee (Climate Dynamics, 2016)

Indoxyl sulfate enhances IL-1β-induced E-selectin expression in endothelial cells in acute kidney injury by the ROS/MAPKs/NFκB/AP-1 pathway - Wen-Ching Shen; Chan-Jung Liang; Tao-Ming Huang; Chen-Wei Liu; Shu-Huei Wang; Guang-Huar Young; Jaw-Shiun Tsai; Ying-Chin Tseng; Yu-Sen Peng; Vin-Cent Wu; Yuh-Lien Chen (Archives of Toxicology, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Global Drivers of Russian Timber Harvest - Sai Liang; Sen Guo; Joshua P. Newell; Shen Qu; Yu Feng; Anthony S.F. Chiu; Ming Xu (Journal of Industrial Ecology, 2016)
Summary Russian forest resources are important for global carbon cycling. In contrast to traditional analyses that focus on the harvest and direct use of Russian timber resources (a.k.a. production‐based accounting), this study investigates how the consumption of nations drives Russian timber harvest (a.k.a. consumption‐based accounting or the Russian timber footprint). China is the biggest direct importer and final consumer of Russian timber. The United States, Japan, and major European countries directly import relatively small amounts of Russian timber, but serve to drive large amounts of Russian timber harvest through their final consumption. Through structural path analysis, individual supply chain paths are delineated to show linkages between Russian timber harvest and the final consumption of nations. Findings of this study inform consumption‐side measures for Russian forest conservation, for example, taking shared responsibility and improving the production efficiency of key sectors in consuming nations.

Inhibition of Autophagy by Estradiol Promotes Locomotor Recovery after Spinal Cord Injury in Rats - Chao-Wei Lin; Bi Chen; Ke-Lun Huang; Yu-Sen Dai; Hong-Lin Teng (Neuroscience Bulletin, 2016)

Two new species of Coltricia (Hymenochaetaceae, Basidiomycota) from southern China based on evidence from morphology and DNA sequence data - Lu-Sen Bian; Fang Wu; Yu-Cheng Dai (Mycological Progress, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Vaccination against type 1 angiotensin receptor prevents streptozotocin-induced diabetic nephropathy - Dan Ding; Yimei Du; Zhihua Qiu; Sen Yan; Fen Chen; Min Wang; Shijun Yang; Yanzhao Zhou; Xiajun Hu; Yihuan Deng; Shijia Wang; Liangping Wang; et al. (Journal of Molecular Medicine, 2016)

Groundwater heavy metal levels and associated human health risk in the North China Plain - Wei Li; Ming-yu Wang; Li-ya Liu; Hui-fang Wang; Sen Yu (Arabian Journal of Geosciences, 2015)

Mean Structure and Fluctuations of the Kuroshio East of Taiwan from In Situ and Remote Observations - Ying Jang Yang; Sen Jan; Ming-Hueh Chang; Joe Wang; Vegan Mensah; Tien-Hsia Kuo; Cheng-ju Tsai; Chung Yaung Lee; Magdalena Andres; Luca Centurioni; Yu-Heng Tseng; Wen-Der LIang; et al. (Oceanography, 2015)

Variability in the composition and export of silica in the Huanghe River Basin - XiangBin Ran; Hong Che; JiaYe Zang; YongGui Yu; Sen Liu; LiLi Zheng (Science China Earth Sciences, 2015)

Spatiotemporal computing of cold wave characteristic in recent 52 years: a case study in Guangdong Province, South China - Wei Liu; Si-yu Huang; Dan Li; Chong-yang Wang; Xia Zhou; Shui-sen Chen (Natural Hazards, 2015)

Diversity and functional characterization of bacterial endophytes dwelling in various rice (Oryza sativa L.) tissues, and their seed-borne dissemination into rhizosphere under gnotobiotic P-stress - Asif Hameed; Meng-Wei Yeh; Yu-Ting Hsieh; Wei-Ching Chung; Chaur-Tsuen Lo; Li-Sen Young (Plant and Soil, 2015)

Erythropoietin Attenuates the Apoptosis of Adult Neurons After Brachial Plexus Root Avulsion by Downregulating JNK Phosphorylation and c-Jun Expression and Inhibiting c-PARP Cleavage - Kai Li; Rang-Juan Cao; Xiao-Juan Zhu; Xing-Yu Liu; Long-Yun Li; Shu-Sen Cui (Journal of Molecular Neuroscience, 2015)

Response of shoot growth, photosynthetic capacity, flowering, and fruiting of potted ‘Nagami’ kumquat to different regulated deficit irrigation - Yung-Chiung Chang; Yu-Sen Chang; Lian-Hsiung Lin (Horticulture, Environment, and Biotechnology, 2015)

Identification of Two Cucumber Putative Silicon Transporter Genes in Cucumis sativus - Hua-Sen Wang; Chao Yu; Pei-Pei Fan; Bin-Fu Bao; Tao Li; Zhu-Jun Zhu (Journal of Plant Growth Regulation, 2015)

Degradation of florfenicol in water by UV/Na2S2O8 process - Yu-qiong Gao; Nai-yun Gao; Yang Deng; Da-qiang Yin; Yan-sen Zhang (Environmental Science and Pollution Research, 2015)

Assessing the authenticity of commercial deep-sea drinking water by chemical and isotopic approaches - Tsung-Ren Peng; Wen-Jui Liang; Tsang-Sen Liu; Yu-Wen Lin; Wen-Jun Zhan (Isotopes in Environmental and Health Studies, 2015)

Association between the CYP2E1 polymorphisms and lung cancer risk: a meta-analysis - Xiang-Hua Ye; Liang Song; Ling Peng; Zhibin Bu; Sen-Xiang Yan; Jie Feng; Xin-Li Zhu; Xin-Biao Liao; Xue-Lin Yu; Danfang Yan (Molecular Genetics and Genomics, 2015)

Reconstructing atmospheric CO 2 during the Plio–Pleistocene transition by fossil Typha - Yun‐Jun Bai; Li‐Qun Chen; Parminder S. Ranhotra; Qing Wang; Yu‐Fei Wang; Cheng‐Sen Li (Global Change Biology, 2015)
The Earth has undergone a significant climate switch from greenhouse to icehouse during the Plio–Pleistocene transition ( PPT ) around 2.7–2.4 million years ago (Ma), marked by the intensification of the Northern Hemisphere glaciation ( NHG ) ~2.7 Ma. Evidence based on oceanic CO 2 [( CO 2 ) aq ], supposed to be in close equilibrium with the atmospheric CO 2 [( CO 2 ) atm ], suggests that the CO 2 decline might drive such climate cooling. However, the rarity of direct evidence from [ CO 2 ] atm during the interval prevents determination of the atmospheric CO 2 level and further assessment on the impact of its fluctuation. Here, we reconstruct the [ CO 2 ] atm level during 2.77–2.52 Ma based on a new developed proxy of stomatal index on Typha orientalis leaves from Shanxi, North China, and depict the first [ CO 2 ] atm curve over the past 5 Ma by using stomata‐based [ CO 2 ] atm data. Comparisons of the terrestrial‐based [ CO 2 ] atm and the existed marine‐based [ CO 2 ] aq curves show a similar general trend but with different intensity of fluctuations. Our data reveal that the high peak of [ CO 2 ] atm occurred at 2.77–2.52 Ma with a lower [ CO 2 ] aq background. The subsequent sharp fall in [ CO 2 ] atm level might be responsible for the intensification of the NHG based on their general temporal synchronism. These findings shed a significant light for our understanding toward the [ CO 2 ] atm changes and its ecological impact since 5 Ma.

Comprehensive Evaluation of Scenario Schemes for Multi-objective Decision-making in River Ecological Restoration by Artificially Recharging River - Sen Yu; Mingyu Wang (Water Resources Management, 2014)

Development of 107 SSR markers from whole genome shotgun sequences of Chinese bayberry (Myrica rubra) and their application in seedling identification - Hui-min Jia; Yu-tong Shen; Yun Jiao; Guo-yun Wang; Xiao Dong; Hui-juan Jia; Fang Du; Sen-miao Liang; Chao-chao Zhou; Wei-hua Mao; Zhong-shan Gao (Journal of Zhejiang University-SCIENCE B, 2014)

A tomato endoplasmic reticulum (ER)-type omega-3 fatty acid desaturase (LeFAD3) functions in early seedling tolerance to salinity stress - Hua-Sen Wang; Chao Yu; Xian-Feng Tang; Zhu-Jun Zhu; Na-Na Ma; Qing-Wei Meng (Plant Cell Reports, 2014)

Association between the TP53 polymorphisms and lung cancer risk: a meta-analysis - Xiang-Hua Ye; Zhi-Bin Bu; Jie Feng; Ling Peng; Xin-Biao Liao; Xin-Li Zhu; Xiao-li Sun; Hao-Gang Yu; Dan-Fang Yan; Sen-Xiang Yan (Molecular Biology Reports, 2014)

Multigene engineering of starch biosynthesis in maize endosperm increases the total starch content and the proportion of amylose - Lili Jiang; Xiaoming Yu; Xin Qi; Qian Yu; Sen Deng; Bing Bai; Ning Li; Ai Zhang; Changfu Zhu; Bao Liu; Jinsong Pang (Transgenic Research, 2013)

The E ocene climate of C hina, the early elevation of the T ibetan P lateau and the onset of the A sian M onsoon - Qing Wang; Robert A. Spicer; Jian Yang; Yu‐Fei Wang; Cheng‐Sen Li (Global Change Biology, 2013)
Eocene palynological samples from 37 widely distributed sites across C hina were analysed using co‐existence approach to determine trends in space and time for seven palaeoclimate variables: Mean annual temperature, mean annual precipitation, mean temperature of the warmest month, mean temperature of the coldest month, mean annual range of temperature, mean maximum monthly precipitation and mean minimum monthly precipitation. Present day distributions and observed climates within C hina of the nearest living relatives of the fossil forms were used to find the range of a given variable in which a maximum number of taxa can coexist. Isotherm and isohyet maps for the early, middle and late E ocene were constructed. These illustrate regional changing patterns in thermal and precipitational gradients that may be interpreted as the beginnings of the modern A sian M onsoon system, and suggest that the uplift of parts of the T ibetan P lateau appear to have taken place by the middle to late E ocene.

The short chain cell-permeable ceramide (C6) restores cell apoptosis and perifosine sensitivity in cultured glioblastoma cells - Li-sen Qin; Zheng-quan Yu; Shi-ming Zhang; Guan Sun; Jian Zhu; Jin Xu; Jun Guo; Lin-shan Fu (Molecular Biology Reports, 2013)

Antisense-mediated depletion of GMPase gene expression in tobacco decreases plant tolerance to temperature stresses and alters plant development - Hua-Sen Wang; Zhu-Jun Zhu; Zhen Feng; Shi-Gang Zhang; Chao Yu (Molecular Biology Reports, 2012)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Folic acid inhibits endothelial cell proliferation through activating the cSrc/ERK 2/NF-κB/p53 pathway mediated by folic acid receptor - Shyr-Yi Lin; Woan-Ruoh Lee; Yi-Fan Su; Sung-Po Hsu; Hsu-Chen Lin; Pei-Yin Ho; Tien-Chi Hou; Yu-Pei Chou; Chun-Ting Kuo; Wen-Sen Lee (Angiogenesis, 2012)

Strengthening of paleo‐typhoon and autumn rainfall in Taiwan corresponding to the Southern Oscillation at late Holocene - Huei‐Fen Chen; Shie‐Ying Wen; Shen‐Rong Song; Tien‐Nan Yang; Teh‐Quei Lee; Sue‐Fen Lin; Shih‐Chieh Hsu; Kuo‐Yen Wei; Ping‐Yu Chang; Pai‐Sen Yu (Journal of Quaternary Science, 2012)
The purpose of this study is to improve prehistoric knowledge of paleo‐typhoon and winter monsoon activity in the western North Pacific after 8 cal. ka BP. We examine two sediment cores derived from lakes located to the south and north of the Ilan Plain in northeastern Taiwan. Seasonal and typhoon rainfall data over the past several decades are collected for this study region. We also use mineral indicators, K/Rb ratios and grain size to estimate sediment sources, intensity of chemical weathering and rainfall intensity. The results show that the chemical weathering index (K/Rb ratio) of Meihua Lake indicates the continuing effects of autumn rainfall, while coarse grain sizes of Dahu Lake sediments suggest increased intensity in typhoon rainfall. Grain size results reveal that increasing El Niño–Southern Oscillation intensity in the tropical Pacific has intensified the activity of super typhoons in the western North Pacific. Finally, we find that frequent activity of super paleo‐typhoons occurred in Taiwan during the La Niña‐like state, and the strengthening winter monsoon activity and higher sea surface temperature enhanced plentiful autumn rainfall in El Niño‐like state. After comparing our results with the paleo‐typhoon data in Japan and south China, we suggest that the tracks of super typhoon are mainly affected by variations in the warm pool and subtropical Northwestern Pacific High in the western Pacific. Copyright © 2012 John Wiley & Sons, Ltd.

Influences of extratropical water masses on equatorial Pacific cold tongue variability during the past 160 ka as revealed by faunal evidence of planktic foraminifers - Pai‐Sen Yu; Markus Kienast; Min‐Te Chen; Isabel Cacho; Jos Abel Flores; Mahyar Mohtadi; Alan C. Mix (Journal of Quaternary Science, 2012)
Glacial cooling (∼1–5°C) in the eastern equatorial Pacific (EEP) cold tongue is often attributed to increased equatorial upwelling, stronger advection from the Peru–Chile Current (PCC), and to the more remote subpolar southeastern Pacific water mass. However, evidence is scarce for identifying unambiguously which process plays a more important role in driving the large glacial cooling in the EEP. To address this question, here we adopt a faunal calibration approach using planktic foraminifers with a new compilation of coretop data from the eastern Pacific, and present new downcore variation data of fauna assemblage and estimated sea surface temperatures (SSTs) for the past 160 ka (Marine Isotope Stage (MIS) 6) from ODP Site 1240 in the EEP. With significant improvement achieved by adding more coretop data from the eastern boundary current, our downcore calibration results indicate that most of the glacial cooling episodes over the past 160 ka in the EEP are attributable to increased influence from the subpolar water mass from high latitudes of the southern Pacific. By applying this new calibration of the fauna SST transfer function to a latitudinal transect of eastern Pacific (EP) cores, we find that the subpolar water mass has been a major dynamic contributor to EEP cold tongue cooling since MIS 6. Copyright © 2012 John Wiley & Sons, Ltd.

Detrimental Effects of Maternal Lead Exposure during Pregnancy and Lactation on Molar Development in the Young Rat - Hong-Sen Chen; Yu-Chen Tsai; Ker-Kong Chen; Yu-Chuan Tseng; Kun-Jung Hsu (Bulletin of Environmental Contamination and Toxicology, 2012)

Aluminum ammonium sulfate dodecahydrate purified from traditional Chinese medicinal herb Korean monkshood root is a potent matrix metalloproteinase inhibitor - Yehua Shen; Sen Liu; Fenghai Jin; Tianyang Mu; Cong Li; Kun Jiang; Weihua Tian; Dahai Yu; Yingqi Zhang; Xuexun Fang (BioMetals, 2012)

Construction of a eukaryotic expression vector pEGFP-C1-BMP-2 and its effect on cell migration - Xiao-ying Wang; Zhong-hua Chen; Ru-yi Zhang; Sen-quan Liu; Zhu Mei; Ying-ying Yu; Xiong Zhang; Qiang Xia; Yue-min Ding (Journal of Zhejiang University-SCIENCE B, 2012)

Growth and union acclimation process of sweet pepper grafted by a tubing-grafting robotic system - Yung-Chiung Chang; Suming Chen; Yi-Chich Chiu; Lian-Hsiung Lin; Yu-Sen Chang (Horticulture, Environment, and Biotechnology, 2012)

Acoustic adaptations to anthropogenic noise in the cicada Cryptotympana takasagona Kato (Hemiptera: Cicadidae) - Bao-Sen Shieh; Shih-Hsiung Liang; Chao-Chieh Chen; Hsiang-Hao Loa; Chen-Yu Liao (acta ethologica, 2012)

Effect of protein restriction with subsequent re-alimentation on compensatory growth of juvenile soft-shelled turtles (Pelodiscus sinensis) - Quan-Sen Xie; Zhen-Cai Yang; Jun-Wei Li; Yu-Juan Li (Aquaculture International, 2012)

Mean Structure and Variability of the Cold Dome Northeast of Taiwan - Sen Jan; Chung-Chi Chen; Ya-Ling Tsai; Yiing Jiang Yang; Joe Wang; Ching-Sheng Chern; Glen Gawarkiewicz; Ren-Chieh Lien; Luca Centurioni; Jia-Yu Kuo (Oceanography, 2011)

Interleukin 29 enhances expression of toll receptor 3 and mediates antiviral signals in human keratinocytes - Sheng-Quan Zhang; Zheng Zhang; Xin Luo; Sen Yang; Yu Chai; Hai-Liang Huang; Xian-Yong Yin; Dao-Jun Hu; Chun-Jun Yang; Jun-Lin Liu; Xue-Jun Zhang (Inflammation Research, 2011)

Overexpression in tobacco of a tomato GMPase gene improves tolerance to both low and high temperature stress by enhancing antioxidation capacity - Hua-Sen Wang; Chao Yu; Zhu-Jun Zhu; Xian-Chang Yu (Plant Cell Reports, 2011)

Th17 promotes acute rejection following liver transplantation in rats - Xiao-jun Xie; Yu-fu Ye; Lin Zhou; Hai-yang Xie; Guo-ping Jiang; Xiao-wen Feng; Yong He; Qin-fen Xie; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Derived vascular endothelial cells induced by mucoepidermoid carcinoma cells: 3-dimensional collagen matrix model - Sen Yang; Li-juan Guo; Qing-hong Gao; Ming Xuan; Ke Tan; Qiang Zhang; Yu-ming Wen; Chang-mei Wang; Xiu-fa Tang; Xiao-yi Wang (Journal of Zhejiang University-SCIENCE B, 2010)

5,5-Diphenyl-2-thiohydantoin-N10 (DPTH-N10) suppresses proliferation of cultured colon cancer cell line COLO-205 by inhibiting DNA synthesis and activating apoptosis - Tong-Sheng Lee; Li-Ching Chen; Yuan Liu; Jender Wu; Yu-Chih Liang; Wen-Sen Lee (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

TCF1 and β-catenin regulate T cell development and function - Qing Yu; Archna Sharma; Jyoti Misra Sen (Immunologic Research, 2010)

Paleoenvironmental inferences from diatom assemblages of the middle Miocene Shanwang Formation, Shandong, China - Ya-Meng Li; David K. Ferguson; Yu-Fei Wang; Cheng-Sen Li (Journal of Paleolimnology, 2010)

An Early Pliocene lake and its surrounding vegetation in Zhejiang, East China - Jin-Feng Li; Ya-Qin Hu; David Kay Ferguson; Yu-Fei Wang; Cheng-Sen Li (Journal of Paleolimnology, 2010)

Early Paleocene vegetation and climate in Jiayin, NE China - Hui Hao; David K. Ferguson; Guang-Ping Feng; Albert Ablaev; Yu-Fei Wang; Cheng-Sen Li (Climatic Change, 2010)

Sources of water in the Taiwan Strait - Sen Jan; Yu-Heng Tseng; David E. Dietrich (Journal of Oceanography, 2010)

An easy-to-use site-directed mutagenesis method with a designed restriction site for convenient and reliable mutant screening - Bao-zhong Zhang; Xin Zhang; Xiao-ping An; Duo-liang Ran; Yu-sen Zhou; Jun Lu; Yi-gang Tong (Journal of Zhejiang University-SCIENCE B, 2009)

Anoxia survival in common carp and crucian carp is related to high zinc concentration in tissues - Sen Shyong JENG; Tzu Yung LIN; Ming Shyong WANG; Yu Yin CHANG; Chao Yi CHEN; Chih Chieh CHANG (Fisheries Science, 2008)

Purification and characterization of a novel neutral β-glucanase and an alkaline β-glucanase from an alkaliphilic Bacillus isolate - Sen-Lin Liu; Wei-Zhao Chen; Yong Wang; Gang Liu; Shao-Wen Yu; Miao Xing (World Journal of Microbiology and Biotechnology, 2008)

Population Genetics and Phylogeography of Bufo gargarizans in China - Yu-Ling Hu; Xiao-Bing Wu; Zhi-Gang Jiang; Peng Yan; Xia Su; Sen-Yang Cao (Biochemical Genetics, 2007)

The Reconstruction of Paleovegetation and Paleoclimate in the Late Pliocene of West Yunnan, China - Xiang-Yu Kou; David K. Ferguson; Jing-Xian Xu; Yu-Fei Wang; Cheng-Sen Li (Climatic Change, 2006)

Establishing the Database of Inundation Potential in Taiwan - Albert S. Chen; Ming-Hsi Hsu; Wei-Hsien Teng; Chen-Jia Huang; Sen-Hae Yeh; Wan-Yu Lien (Natural Hazards, 2006)

Direct organogenesis and plantlet regeneration from mature zygotic embryos of masson pine (Pinus massoniana L.) - Yu Zhang; Zhi-ming Wei; Meng-li Xi; Ji-sen Shi (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Status, causes and combating suggestions of sandy desertification in qinghai-tibet plateau - Yi-hua Liu; Guang-rong Dong; Sen Li; Yu-xiang Dong (Chinese Geographical Science, 2005)

The wheat TaGI1, involved in photoperiodic flowering, encodesan Arabidopsis GI ortholog - Xiang Yu Zhao; Mao Sen Liu; Jia Rui Li; Chun Mei Guan; Xian Sheng Zhang (Plant Molecular Biology, 2005)

Antitermitic and Antifungal Activities of Essential Oil of Calocedrus formosana Leaf and Its Composition - Sen-Sung Cheng; Chi-Lin Wu; Hui-Ting Chang; Yu-Ting Kao; Shang-Tzen Chang (Journal of Chemical Ecology, 2004)

Evidence for aburpt climatic changes on northwestern margin of east Asian monsoon region during last deglaciation - Ming-rui Qiang; Sen Li; Shang-yu Gao (Chinese Geographical Science, 2004)

Circulation and Brackish Water Dispersal in a Coastal Lagoon of Southwest Taiwan - Sen Jan; Shenn-Yu Chao; Jia-Jang Hung (Journal of Oceanography, 2001)

Autotoxic potential of cucurbit crops - Jing Quan Yu; Sen Yan Shou; Ya Rong Qian; Zhu Jun Zhu; Wen Hai Hu (Plant and Soil, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Overexpression of transfected human ribonucleotide reductase M2 subunit in human cancer cells enhances their invasive potential - Bing-Sen Zhou; Pamela Tsai; Rhonda Ker; Jeffrey Tsai; Roger Ho; Johnathan Yu; Jennifer Shih; Yun Yen (Clinical & Experimental Metastasis, 1998)